Resin composition

The resin composition with a specific organic filler and curable resin addresses high dielectric loss and blistering issues, providing low dielectric loss tangent, crack resistance, and improved insulation reliability for circuit boards and semiconductor chip packages.

JP7601049B2Active Publication Date: 2024-12-17AJINOMOTO CO INC
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2022076082
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-05-02
Publication Date
2024-12-17
Estimated Expiration
2042-05-02

AI Technical Summary

Technical Problem

Conventional resin compositions containing organic fillers for insulating layers in circuit boards and semiconductor chip packages face issues with high dielectric loss tangent, increased transmission loss at high temperatures, and poor insulation reliability due to blistering during the reflow process, which are exacerbated by the use of polystyrene particles.

Method used

A resin composition comprising an organic filler with a specific polymer containing a repeating unit and a curable resin, where the organic filler has an average particle size of 5 μm or less, and optionally includes an inorganic filler, curable resins like epoxy, phenol, or active ester resins, and a shell portion exposed on the surface of the organic filler particles, to improve crack resistance and reduce dielectric loss tangent.

Benefits of technology

The composition achieves a low dielectric loss tangent, excellent crack resistance, and blister resistance, along with high temperature stability and improved insulation reliability, suitable for forming insulating layers in circuit boards and semiconductor chip packages.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007601049000014
    Figure 0007601049000014
  • Figure 0007601049000001
    Figure 0007601049000001
  • Figure 0007601049000002
    Figure 0007601049000002
Patent Text Reader

Abstract

To provide a resin composition that can yield an insulating layer with a low dielectric loss tangent, and superior crack resistance and blister resistance.SOLUTION: A resin composition includes (A) an organic filler including a polymer with a specific repeat unit and (B) a curable resin, with the (A) organic filler having an average particle size of 5 μm or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, and a sheet-like laminate material, a resin sheet, a circuit board, a semiconductor chip package, and a semiconductor device each using the resin composition. [Background technology]

[0002] In general, an insulating layer is provided on a circuit board and a semiconductor chip package. For example, an interlayer insulating layer may be provided as an insulating layer on a printed wiring board, which is a type of circuit board. In addition, for example, a rewiring formation layer may be provided as an insulating layer on a semiconductor chip package. These insulating layers are usually formed of a cured product obtained by curing a resin composition. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-23714 A [Patent Document 2] JP 2020-83966 A [Patent Document 3] JP 2020-136542 A [Patent Document 4] Patent No. 6859897 Summary of the Invention [Problem to be solved by the invention]

[0004] In recent years, with the progress of high density wiring in circuit boards and semiconductor chip packages, there is a demand for improving the crack resistance of insulating layers. The present inventors have attempted to use an organic filler to improve crack resistance. In a cured product of a resin composition containing an appropriate organic filler, the organic filler acts as a component that can relieve stress (stress relaxation component), so that it is expected to improve crack resistance.

[0005] However, as a result of further investigations, the present inventors have found the following first and second problems in resin compositions containing an organic filler.

[0006] First, when a conventional organic filler is used as a stress relaxation component, the dielectric tangent of the cured product becomes high, which may lead to large transmission loss. In addition, some organic fillers such as polystyrene particles can improve crack resistance and reduce the dielectric tangent, but tend to cause blisters during the reflow process. Here, blisters refer to the phenomenon in which the conductor layer rises and swells during reflow.

[0007] Therefore, a first object of the present invention is to provide a resin composition capable of obtaining an insulating layer having a low dielectric tangent and excellent crack resistance and blister resistance; a sheet-like laminate material and a resin sheet containing the resin composition; and a circuit board, a semiconductor chip package, and a semiconductor device each containing a cured product of the resin composition.

[0008] Secondly, when a conventional organic filler is used as a stress relaxation component, the dielectric loss tangent of the cured product of the resin composition tends to have poor temperature stability at high temperatures. Specifically, the dielectric loss tangent of the cured product in a high temperature environment tends to increase significantly compared to the dielectric loss tangent of the cured product in a normal temperature environment. In general, circuit boards and semiconductor chip packages generate heat during use. Therefore, when a cured product whose dielectric loss tangent increases significantly in a high temperature environment is used as described above, the transmission loss may increase in a high temperature environment. In addition, when a conventional organic filler is used, the insulation reliability of the insulating layer tends to be poor.

[0009] Therefore, a second object of the present invention is to provide a resin composition capable of obtaining an insulating layer having excellent crack resistance, temperature stability of dielectric tangent at high temperatures, and insulation reliability; a sheet-like laminate material and a resin sheet containing the resin composition; and a circuit board, a semiconductor chip package, and a semiconductor device each containing a cured product of the resin composition. [Means for solving the problem]

[0010] The present inventors have conducted extensive research to solve the above problems, and as a result, have found that a resin composition containing (A) an organic filler containing a polymer containing a specific repeating unit and (B) a curable resin, in which the average particle size of the organic filler (A) is within a specific range, can solve the above problems, and have completed the present invention. That is, the present invention includes the following.

[0011] <1> (A) an organic filler containing a polymer containing a repeating unit represented by the following formula (1), and (B) a curable resin, (A) A resin composition, in which the average particle size of the organic filler is 5 μm or less. [ka] (In formula (1), R a each independently represents a hydrogen atom or a monovalent saturated hydrocarbon group, R b represents a hydrogen atom or a monovalent hydrocarbon group which may have a substituent. <2> (C) further comprising an inorganic filler; <1> The resin composition according to claim 1. <3> (B) the curable resin includes at least one selected from the group consisting of an epoxy resin, a phenolic resin, an active ester resin, a cyanate resin, a (meth)acrylic resin, a styryl resin, a propenyl resin, and a maleimide resin; <1> or <2> The resin composition according to claim 1. <4> The particles of the organic filler (A) include a shell portion exposed on a surface of the particles of the organic filler (A), The shell portion contains a polymer containing a repeating unit represented by formula (1). <1> ~ <3> The resin composition according to any one of claims 1 to 7. <5> (A) the average particle size of the organic filler is 1 μm or less; <1> ~ <4> The resin composition according to any one of claims 1 to 7. <6> (B) the curable resin includes an active ester resin; <1> ~ <5> The resin composition according to any one of claims 1 to 7. <7> The rate of increase of Df(100°C) relative to Df(25°C) is less than 20%; Df(25°C) represents the dielectric tangent at 25°C of a cured product obtained by heat-treating a resin composition at 200°C for 90 minutes, Df(100°C) represents the dielectric tangent at 100°C of the cured product obtained by heat-treating the resin composition at 200°C for 90 minutes. <1> ~ <6> The resin composition according to any one of claims 1 to 7. <8> (A) the amount of the organic filler is 0.2% by mass or more and 5% by mass or less based on 100% by mass of the non-volatile components of the resin composition; <1> ~ <7> The resin composition according to any one of claims 1 to 7. <9> For forming an insulating layer. <1> ~ <8> The resin composition according to any one of claims 1 to 7. <10> <1> ~ <9> 13. A cured product of the resin composition according to any one of claims 1 to 12. <11> <1> ~ <9> A sheet-like laminate material comprising the resin composition according to any one of claims 1 to 5. <12> A support and a resin composition layer formed on the support, The resin composition layer is <1> ~ <9> A resin sheet comprising the resin composition according to any one of claims 1 to 10. <13> <1> ~ <9> A circuit board comprising a cured product of the resin composition according to any one of claims 1 to 5. <14> <1> ~ <9> 13. A semiconductor chip package comprising a cured product of the resin composition according to any one of claims 1 to 12. <15> <13> A semiconductor device comprising the circuit board according to claim 1. <16> <14> A semiconductor device comprising the semiconductor chip package according to claim 1.

[0012] In particular, from the viewpoint of solving the first problem, the following is desirable. <i-1>(A) an organic filler containing a polymer containing a repeating unit represented by formula (1) and (B) a curable resin, (A) A resin composition, in which the average particle size of the organic filler is 5 μm or less. <i-2>(C) further comprising an inorganic filler; <i-1>The resin composition according to claim 1. <i-3>(B) the curable resin includes at least one selected from the group consisting of an epoxy resin, a phenolic resin, an active ester resin, a cyanate resin, a (meth)acrylic resin, a styryl resin, a propenyl resin, and a maleimide resin; <i-1>or <i-2>The resin composition according to claim 1. <i-4>The particles of the organic filler (A) include a shell portion exposed on a surface of the particles of the organic filler (A), The shell portion contains a polymer containing a repeating unit represented by formula (1). <i-1> ~ <i-3>The resin composition according to any one of claims 1 to 7. <i-5>(A) the average particle size of the organic filler is 1 μm or less; <i-1> ~ <i-4>The resin composition according to any one of claims 1 to 7. <i-6>For forming an insulating layer. <i-1> ~ <i-5>The resin composition according to any one of claims 1 to 7. <i-7> <i-1> ~ <i-6>13. A cured product of the resin composition according to any one of claims 1 to 12. <i-8> <i-1> ~ <i-6>A sheet-like laminate material comprising the resin composition according to any one of claims 1 to 5. <i-9>A support and a resin composition layer formed on the support, The resin composition layer is <i-1> ~ <i-6>A resin sheet comprising the resin composition according to any one of claims 1 to 10. <i-10> <i-1> ~ <i-6>A circuit board comprising a cured product of the resin composition according to any one of claims 1 to 5. <i-11> <i-1> ~ <i-6>13. A semiconductor chip package comprising a cured product of the resin composition according to any one of claims 1 to 12. <i-12> <i-10>or the circuit board according to <i-11>A semiconductor device comprising the semiconductor chip package according to claim 1.

[0013] In particular, from the viewpoint of solving the second problem, the following is preferable. <ii-1>(A) an organic filler containing a polymer containing a repeating unit represented by formula (1) and (B) a curable resin, (A) A resin composition, in which the average particle size of the organic filler is 5 μm or less. <ii-2>(C) further comprising an inorganic filler; <ii-1>The resin composition according to claim 1. <ii-3>(B) the curable resin includes at least one selected from the group consisting of an epoxy resin, a phenolic resin, an active ester resin, a cyanate resin, a (meth)acrylic resin, a styryl resin, a propenyl resin, and a maleimide resin; <ii-1>or <ii-2>The resin composition according to claim 1. <ii-4>The particles of the organic filler (A) include a shell portion exposed on a surface of the particles of the organic filler (A), The shell portion contains a polymer containing a repeating unit represented by formula (1). <ii-1> ~ <ii-3>The resin composition according to any one of claims 1 to 7. <ii-5>(B) the curable resin includes an active ester resin; <ii-1> ~ <ii-4>The resin composition according to any one of claims 1 to 7. <ii-6>The rate of increase of Df(100°C) relative to Df(25°C) is less than 20%; Df(25°C) represents the dielectric tangent at 25°C of a cured product obtained by heat-treating a resin composition at 200°C for 90 minutes, Df(100°C) represents the dielectric tangent at 100°C of the cured product obtained by heat-treating the resin composition at 200°C for 90 minutes. <ii-1> ~ <ii-5>The resin composition according to any one of claims 1 to 7. <ii-7>(A) the amount of the organic filler is 0.2% by mass or more and 5% by mass or less based on 100% by mass of the non-volatile components of the resin composition; <ii-1> ~ <ii-6>The resin composition according to any one of claims 1 to 7. <ii-8>For forming an insulating layer. <ii-1> ~ <ii-7>The resin composition according to any one of claims 1 to 7. <ii-9> <ii-1> ~ <ii-8>13. A cured product of the resin composition according to any one of claims 1 to 12. <ii-10> <ii-1> ~ <ii-8>13. A sheet-like laminate material comprising the resin composition according to claim 12. <ii-11>A support and a resin composition layer formed on the support, The resin composition layer is <ii-1> ~ <ii-8>A resin sheet comprising the resin composition according to any one of claims 1 to 10. <ii-12> <ii-1> ~ <ii-8>A circuit board comprising a cured product of the resin composition according to any one of claims 1 to 5. <ii-13> <ii-1> ~ <ii-8>13. A semiconductor chip package comprising a cured product of the resin composition according to any one of claims 1 to 12. <ii-14> <ii-12>or the circuit board according to <ii-13>A semiconductor device comprising the semiconductor chip package according to claim 1. Effect of the Invention

[0014] According to the resin composition of the present invention, at least one of the following first and second effects can be obtained. First, the present invention can provide a resin composition capable of obtaining an insulating layer having a low dielectric tangent and excellent crack resistance and blister resistance; a sheet-like laminate material and a resin sheet containing the resin composition; and a circuit board, a semiconductor chip package, and a semiconductor device each containing a cured product of the resin composition. Secondly, according to the present invention, there can be provided a resin composition capable of obtaining an insulating layer having excellent crack resistance, temperature stability of dielectric tangent at high temperatures, and insulation reliability; a sheet-like laminate material and a resin sheet containing the resin composition; and a circuit board, a semiconductor chip package, and a semiconductor device each containing a cured product of the resin composition. [Brief description of the drawings]

[0015] [Figure 1] FIG. 1 is a cross-sectional view showing a schematic diagram of a fan-out type WLP as an example of a semiconductor chip package according to an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The present invention will be described below with reference to embodiments and examples. However, the present invention is not limited to the embodiments and examples shown below, and may be modified and implemented as desired without departing from the scope of the claims and their equivalents.

[0017] In the following description, the term "(meth)acrylic acid" includes acrylic acid, methacrylic acid, and combinations thereof, and the term "(meth)acrylate" includes acrylate, methacrylate, and combinations thereof.

[0018] In the following description, the term "dielectric constant" refers to the relative dielectric constant unless otherwise specified.

[0019] <Outline of resin composition according to the first embodiment> The resin composition according to the first embodiment of the present invention contains a combination of an organic filler (A) and a curable resin (B). The organic filler (A) contains a polymer containing a repeating unit represented by the following formula (1). The organic filler (A) has an average particle size within a specific range. Hereinafter, the polymer containing the repeating unit represented by formula (1) may be referred to as "polymer (1)" as appropriate.

[0020] [ka] (In formula (1), R a each independently represents a hydrogen atom or a monovalent saturated hydrocarbon group, R b represents a hydrogen atom or a monovalent hydrocarbon group which may have a substituent.

[0021] According to the resin composition according to the first embodiment, an insulating layer having a low dielectric tangent and excellent crack resistance and blister resistance can be obtained. In addition, this insulating layer can usually have a low relative dielectric constant.

[0022] <(A) Organic Filler According to the First Embodiment> The resin composition according to the first embodiment of the present invention contains an organic filler (A) as component (A). This organic filler (A) is present in the resin composition in particulate form, and is usually included in the cured product while maintaining the particulate form.

[0023] The (A) organic filler contains a polymer (1) containing a repeating unit represented by formula (1). The (A) organic filler containing the polymer (1) can usually exert an effect of relaxing stress in the cured product of the resin composition, and therefore can improve the crack resistance of the cured product. In addition, the cured product usually has low polarity, and therefore can reduce dielectric properties such as dielectric loss tangent.

[0024] [ka]

[0025] In formula (1), R a each independently represents a hydrogen atom or a monovalent saturated hydrocarbon group. The monovalent saturated hydrocarbon group may be a chain hydrocarbon group that does not contain a ring structure, or may be a cyclic hydrocarbon group that contains a ring structure. Among these, the monovalent saturated hydrocarbon group is preferably an alkyl group. a The number of carbon atoms in the monovalent saturated hydrocarbon group as R is usually 1 or more, and usually 12 or less, preferably 8 or less, and particularly preferably 6 or less. Preferred examples of the monovalent saturated hydrocarbon group include alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, and hexyl groups; and cycloalkyl groups such as cyclohexyl groups. Among these, R a is preferably a hydrogen atom.

[0026] In formula (1), R b represents a hydrogen atom or a monovalent hydrocarbon group which may have a substituent. The monovalent hydrocarbon group may be a chain hydrocarbon group which does not contain a ring structure, or may be a cyclic hydrocarbon group which contains a ring structure. The monovalent hydrocarbon group may be a saturated hydrocarbon group or an unsaturated hydrocarbon group. The monovalent hydrocarbon group may be an aliphatic hydrocarbon group or an aromatic hydrocarbon group. R b The number of carbon atoms in the monovalent hydrocarbon group as is usually 1 or more and usually 18 or less, preferably 12 or less, more preferably 8 or less, and particularly preferably 6 or less. Preferred monovalent hydrocarbon groups include, for example, alkyl groups such as methyl, ethyl, propyl, butyl, pentyl, and hexyl groups; alkenyl groups such as vinyl groups; cycloalkyl groups such as cyclohexyl groups; aryl groups such as phenyl and naphthyl groups; and alkylaryl groups such as methylphenyl and ethylphenyl groups.

[0027] R b The monovalent hydrocarbon group may have a substituent. Unless otherwise specified, the term "optionally substituted" of a hydrocarbon group means both the case where the hydrogen atoms of the hydrocarbon group are not substituted with a substituent and the case where some or all of the hydrogen atoms of the hydrocarbon group are substituted with a substituent. Examples of the substituent include a halogen atom, an alkoxy group, a cycloalkyloxy group, an aryloxy group, an arylalkoxy group, a monovalent heterocyclic group, an amino group, a silyl group, an acyl group, an acyloxy group, a carboxy group, a sulfo group, a cyano group, a nitro group, a hydroxy group, a mercapto group, and an oxo group. Among them, a hydroxy group and a carboxy group are preferred, and a carboxy group is particularly preferred.

[0028] Among the above, R b is preferably a monovalent cyclic hydrocarbon group which may have a substituent, more preferably an aryl group which may have a hydroxy group, a carboxy group, or an alkyl group, even more preferably an aryl group which may have a hydroxy group or a carboxy group, even more preferably an aryl group which may have a carboxy group, even more preferably an unsubstituted aryl group, and particularly preferably a phenyl group.

[0029] Examples of the repeating unit represented by formula (1) include those represented by the following formulas (1-1) to (1-5). Among them, the repeating unit represented by formula (1-1) and the repeating unit represented by formula (1-5) are preferred.

[0030] [ka]

[0031] The polymer (1) preferably contains a large amount of the repeating unit represented by formula (1), and may contain only the repeating unit represented by formula (1). The amount of the repeating unit represented by formula (1) is preferably 30% by mass or more, more preferably 50% by mass or more, even more preferably 70% by mass or more, particularly preferably 90% by mass or more, and is usually 100% by mass or less, based on the total mass (100% by mass) of the polymer (1).

[0032] The polymer (1) may be a homopolymer or a copolymer. Thus, the polymer (1) may be a homopolymer containing only one repeating unit represented by formula (1), or a copolymer containing two or more repeating units represented by formula (1). Furthermore, the polymer (1) may be a copolymer containing a combination of a repeating unit represented by formula (1) and any repeating unit not represented by formula (1).

[0033] When the polymer (1) is a copolymer containing an optional repeating unit, the optional repeating unit may have a structure formed by polymerizing an optional monomer. Examples of the optional monomer include (meth)acrylic acid esters such as methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, cyclohexyl (meth)acrylate, octyl (meth)acrylate, and glycidyl (meth)acrylate; (meth)acrylic acid; N-substituted maleimides such as N-methylmaleimide and N-phenylmaleimide; maleimide; α,β-unsaturated carboxylic acids such as maleic acid and itaconic acid; and the like. The optional monomer may be used alone or in combination of two or more kinds. Thus, the polymer (1) may contain only one type of the optional repeating unit, or in combination of two or more kinds.

[0034] The amount of any repeating unit in the polymer (1) is preferably small. The amount of any repeating unit is preferably 70% by mass or less, more preferably 50% by mass or less, further preferably 30% by mass or less, particularly preferably 10% by mass or less, and may be 0% by mass, based on the total mass of the polymer (1) (100% by mass).

[0035] The glass transition temperature of the polymer (1) is preferably 20° C. or higher, more preferably 50° C. or higher, particularly preferably 80° C. or higher, and is preferably 180° C. or lower, more preferably 150° C. or lower, particularly preferably 120° C. or lower. The glass transition temperature of the polymer (1) can be measured by DSC (differential scanning calorimetry) at a heating rate of 10° C. / min.

[0036] The (A) organic filler preferably contains a large amount of polymer (1), and may contain only polymer (1). The amount of polymer (1) is preferably 30% by mass or more, more preferably 50% by mass or more, even more preferably 70% by mass or more, particularly preferably 90% by mass or more, and is usually 100% by mass or less, based on 100% by mass of the (A) organic filler.

[0037] The (A) organic filler may contain an optional component in combination with the polymer (1). The optional component other than the polymer (1) that the (A) organic filler may contain may be, for example, an optional polymer. Examples of the optional polymer include acrylic polymers such as polymethyl(meth)acrylate, polyethyl(meth)acrylate, polypropyl(meth)acrylate, polybutyl(meth)acrylate, polycyclohexyl(meth)acrylate, and polyoctyl(meth)acrylate; and silicone polymers such as polydimethylsiloxane. One type of optional component may be used alone, or two or more types may be used in combination.

[0038] The amount of optional components in the (A) organic filler is preferably small. The amount of optional components that the (A) organic filler may contain is preferably 70% by mass or less, more preferably 50% by mass or less, still more preferably 30% by mass or less, particularly preferably 10% by mass or less, and may even be 0% by mass, based on 100% by mass of the (A) organic filler.

[0039] The particles of the (A) organic filler may have a uniform composition throughout the particle, or the particles may have a non-uniform composition. When the portions contained in the particles of the (A) organic filler are divided according to composition, the particles usually include a shell portion exposed on the surface of the particle. This shell portion corresponds to the outermost layer portion of the particles of the (A) organic filler. Therefore, it can be understood that the particles of the (A) organic filler having a uniform composition are formed entirely by the shell portion. In addition, the particles of the (A) organic filler having a non-uniform composition may have a shell portion and a core portion formed within the shell portion. In this case, the particles of the (A) organic filler may further include an arbitrary portion within the core portion, or may include an arbitrary portion between the shell portion and the core portion. Here, the shell portion and the core portion may not be clearly distinguishable, and the boundary between the shell portion and the core portion may be unclear. Furthermore, the core portion may be covered by the shell portion, or may not be completely covered. Furthermore, the particles of the (A) organic filler may have a hollow portion within the shell portion.

[0040] From the viewpoint of exhibiting the effects of the present invention significantly, it is preferable that the shell portion contains polymer (1). It is preferable that the shell portion contains a large amount of polymer (1), and it may contain only polymer (1). The range of the amount of polymer (1) relative to 100% by mass of the shell portion may be the same as the range of the amount of polymer (1) relative to 100% by mass of the organic filler (A) described above. When the shell portion contains polymer (1), the aggregation of particles of the organic filler (A) can be effectively suppressed, so that the effect of the organic filler (A) can be effectively exhibited. In particular, when the particles of the organic filler (A) contain a combination of a shell portion and a core portion, the degree of freedom of the composition of the core portion covered by the shell portion can be increased.

[0041] Examples of commercially available (A) organic fillers containing the above-mentioned polymer (1) include organic fillers having an average particle size of 1 μm or less, such as "SEP-03T3", "SEP-03T3A", "SSD-001T", "SEP-03T4", "SEP-03T3AB", "SEP-03T3AC", and "SEP-03T3AD" manufactured by Negami Chemical Industries Co., Ltd.; "XX-6283Z", "XX-6288Z", "XX-6145Z", "XX-6229Z", "XX-6283Z", "XX-6214Z (hollow polystyrene)", and "XX-6430Z (hollow polystyrene)" manufactured by Sekisui Chemical Co., Ltd.; "PS-050-1" and "PS-050-2" manufactured by Aica Kogyo Co., Ltd.; and "SB-25N" manufactured by Morimoto Chemical Co., Ltd. Further, examples of organic fillers having an average particle size of greater than 1 μm include "GS-0305" (average particle size 3 μm) manufactured by Aica Kogyo Co., Ltd.; "SB-25" (average particle size 2.5 μm) manufactured by Morimoto Chemical Co., Ltd.; and "SX-130H" (average particle size 1.3 μm) manufactured by Soken Chemical & Engineering Co., Ltd.

[0042] The (A) organic filler may be used alone or in combination of two or more kinds.

[0043] The (A) organic filler has an average particle size within a specific range. Specifically, the average particle size of the (A) organic filler is usually 5 μm or less, preferably 3 μm or less, and particularly preferably 1 μm or less. When the average particle size of the particles of the (A) organic filler is small as described above, it is possible to improve not only the dielectric tangent and the crack resistance but also the blister resistance. In detail, it is as follows. A cured product containing an organic filler containing a polymer (1) has traditionally tended to have low adhesion to a conductor layer serving as a base for an insulating layer. Therefore, in the past, when a conductor layer was formed on an insulating layer formed by a cured product and a reflow treatment was performed, the insulating layer peeled off from the conductor layer serving as a base and the conductor layer on the insulating layer easily rose up, so that blisters were likely to occur. In contrast, in the first embodiment of the present invention, by using the (A) organic filler having an average particle size within a specific range, it was possible to suppress blisters while having excellent crack resistance and dielectric properties. The fact that blisters can be suppressed by controlling the average particle size of the (A) organic filler is an effect discovered for the first time by the present inventor, and it can be said to be an unexpected effect from the conventional technical common sense. There is no particular lower limit for the average particle size of the (A) organic filler, and it can be, for example, 0.01 μm or more, 0.05 μm or more, or 0.1 μm or more.

[0044] The average particle size of the (A) organic filler can be measured using a laser diffraction particle size distribution measuring device (e.g., Shimadzu Corporation's "SALD-2100"). With this measuring device, the volume average particle size can be measured as the average particle size of the (A) organic filler. The measurement can be performed by dispersing the (A) organic filler in an organic solvent that does not dissolve the (A) organic filler. As the organic solvent, a low polarity solvent or a medium polarity solvent is usually used, and toluene or tetrahydrofuran (THF) is preferably used, in order to suppress aggregation of the (A) organic filler.

[0045] (A) organic filler may not be treated with a surface treatment agent, or may be treated with a surface treatment agent. Examples of surface treatment agents for (A) organic filler include inorganic acids such as hydrochloric acid, nitric acid, and sulfuric acid; carboxylic acids such as acetic acid, propionic acid, butyric acid, and acrylic acid; sulfonic acids such as p-toluenesulfonic acid, ethylsulfonic acid, and dodecylbenzenesulfonic acid; phosphoric acids such as polyoxyethylene alkyl ether phosphoric acid; organic acids such as phosphonic acid and phosphinic acid; silane coupling agents such as tetraethoxysilane, methyltrimethoxysilane, phenyltrimethoxysilane, 3-(meth)acryloxypropyltrimethoxysilane, and 8-(meth)acryloxyoctyltrimethoxysilane; and isocyanate compounds such as ethyl isocyanate. One type of surface treatment agent may be used alone, or two or more types may be used in combination.

[0046] The amount of the (A) organic filler contained in the resin composition according to the first embodiment of the present invention is preferably 0.2% by mass or more, more preferably 0.5% by mass or more, particularly preferably 1% by mass or more, and is preferably 20% by mass or less, more preferably 10% by mass or less, particularly preferably 5% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the (A) organic filler is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0047] The amount of the (A) organic filler contained in the resin composition according to the first embodiment of the present invention is preferably 0.2% by mass or more, more preferably 1% by mass or more, particularly preferably 2% by mass or more, and preferably 40% by mass or less, more preferably 30% by mass or less, particularly preferably 20% by mass or less, based on 100% by mass of the resin components of the resin composition. The resin components of the resin composition refer to the non-volatile components of the resin composition excluding the (C) inorganic filler. When the amount of the (A) organic filler is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0048] <(B) Curable resin according to the first embodiment> The resin composition according to the first embodiment of the present invention contains a (B) curable resin as the (B) component. The (B) curable resin does not include those corresponding to the above-mentioned (A) component. The (B) curable resin may be a thermosetting resin, a photocurable resin, or a combination of these. In addition, the curable resin may be used alone or in combination of two or more types.

[0049] Examples of the curable resin include epoxy resins, phenol resins, active ester resins, cyanate resins, carbodiimide resins, acid anhydride resins, amine resins, benzoxazine resins, thiol resins, and radical polymerizable resins. One type of curable resin may be used alone, or two or more types may be used in combination.

[0050] In particular, from the viewpoint of obtaining the effects of the present invention significantly, it is preferable to use a combination of an epoxy resin and a resin capable of reacting with the epoxy resin to cure the resin composition. The resin capable of reacting with the epoxy resin to cure the resin composition may be referred to as a "curing agent" hereinafter. Examples of the curing agent include phenolic resin, active ester resin, cyanate resin, carbodiimide resin, acid anhydride resin, amine resin, benzoxazine resin, and thiol resin. Among the curing agents, phenolic resin, active ester resin, cyanate resin, and carbodiimide resin are preferred. In addition, the curing agent may be used alone or in combination of two or more types.

[0051] The epoxy resin is a curable resin having an epoxy group. Examples of epoxy resins include bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, phenol aralkyl type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, isocyanurate type epoxy resins, and phenolphthalimidine type epoxy resins. The epoxy resin may be used alone or in combination of two or more kinds.

[0052] From the viewpoint of obtaining a cured product having excellent heat resistance, the epoxy resin preferably contains an aromatic structure. The aromatic structure is a chemical structure generally defined as aromatic, and includes polycyclic aromatic rings and aromatic heterocycles. Examples of epoxy resins containing an aromatic structure include bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, bisxylenol type epoxy resins, glycidylamine type epoxy resins having an aromatic structure, glycidyl ester type epoxy resins having an aromatic structure, cresol novolac type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins having an aromatic structure, epoxy resins having a butadiene structure having an aromatic structure, alicyclic epoxy resins having an aromatic structure, heterocyclic epoxy resins, spiro ring-containing epoxy resins having an aromatic structure, cyclohexane dimethanol type epoxy resins having an aromatic structure, naphthylene ether type epoxy resins, trimethylol type epoxy resins having an aromatic structure, and tetraphenylethane type epoxy resins having an aromatic structure.

[0053] The (B) curable resin preferably contains, as an epoxy resin, an epoxy resin having two or more epoxy groups in one molecule. The proportion of the epoxy resin having two or more epoxy groups in one molecule relative to 100% by mass of the non-volatile components of the epoxy resin is preferably 50% by mass or more, more preferably 60% by mass or more, and particularly preferably 70% by mass or more.

[0054] Epoxy resins include epoxy resins that are liquid at a temperature of 20° C. (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20° C. (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition may contain only liquid epoxy resins as the epoxy resin, or may contain only solid epoxy resins, or may contain a combination of liquid epoxy resins and solid epoxy resins.

[0055] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.

[0056] As the liquid epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane type epoxy resin, cyclohexane dimethanol type epoxy resin, and epoxy resin having a butadiene structure are preferred.

[0057] Specific examples of liquid epoxy resins include "HP4032", "HP4032D", and "HP4032SS" (naphthalene type epoxy resins) manufactured by DIC Corporation; "828US", "828EL", "jER828EL", "825", and "Epikote 828EL" (bisphenol A type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER807" and "1750" (bisphenol F type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical Corporation; "630", "630LSD", and "604" (glycidylamine type epoxy resins) manufactured by Mitsubishi Chemical Corporation; "ED-523T" (glycirol type epoxy resin) manufactured by ADEKA Corporation; "EP-3950L" and "EP-3980S" ( glycidylamine type epoxy resin); ADEKA's "EP-4088S" (dicyclopentadiene type epoxy resin); Nippon Steel Chemical & Material Chemical's "ZX1059" (mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin); Nagase Chemtex's "EX-721" (glycidyl ester type epoxy resin); Daicel's "Celloxide 2021P" (alicyclic epoxy resin having an ester skeleton); Daicel's "PB-3600", Nippon Soda's "JP-100" and "JP-200" (epoxy resin having a butadiene structure); Nippon Steel Chemical & Material's "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resin), etc. These may be used alone or in combination of two or more types.

[0058] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable.

[0059] Preferred solid epoxy resins include bixylenol type epoxy resins, naphthalene type epoxy resins, naphthalene type tetrafunctional epoxy resins, naphthol novolac type epoxy resins, cresol novolac type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, naphthylene ether type epoxy resins, anthracene type epoxy resins, bisphenol A type epoxy resins, bisphenol AF type epoxy resins, phenol aralkyl type epoxy resins, tetraphenylethane type epoxy resins, and phenolphthalimidine type epoxy resins.

[0060] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene type epoxy resins) manufactured by DIC Corporation; and "EXA-7311" manufactured by DIC Corporation. , "EXA-7311-G3", "EXA-7311-G4", "EXA-7311-G4S", "HP6000" (naphthylene ether type epoxy resin); "EPPN-502H" (trisphenol type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC7000L" (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.; "NC3000H", "NC3000", "NC3000L", "NC3000FH", "NC3100" (biphenyl type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN475V", "ESN4 100V" (naphthalene type epoxy resin); "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN375" (dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK", "YL7890" (bixylenol type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "Y Examples of epoxy resins include "X7700" (phenol aralkyl type epoxy resin); "PG-100" and "CG-500" manufactured by Osaka Gas Chemicals; "YX7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical; "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical; and "WHR991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.These may be used alone or in combination of two or more.

[0061] When a liquid epoxy resin and a solid epoxy resin are used in combination as the epoxy resin, the mass ratio thereof (liquid epoxy resin:solid epoxy resin) is preferably 20:1 to 1:20, more preferably 10:1 to 1:10, and particularly preferably 7:1 to 1:7.

[0062] The epoxy equivalent of the epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 3,000 g / eq., further preferably 80 g / eq. to 2,000 g / eq., and particularly preferably 110 g / eq. to 1,000 g / eq. The epoxy equivalent represents the mass of the resin per equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.

[0063] The weight average molecular weight (Mw) of the epoxy resin is preferably 100 to 5,000, more preferably 250 to 3,000, and further preferably 400 to 1500. The weight average molecular weight of the epoxy resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.

[0064] The amount of the epoxy resin in the resin composition is preferably 1% by mass or more, more preferably 2% by mass or more, particularly preferably 5% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, particularly preferably 30% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the epoxy resin is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0065] The amount of the epoxy resin in the resin composition is preferably 5% by mass or more, more preferably 10% by mass or more, particularly preferably 20% by mass or more, and is preferably 80% by mass or less, more preferably 70% by mass or less, particularly preferably 60% by mass or less, based on 100% by mass of the resin components of the resin composition. When the amount of the epoxy resin is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0066] As the phenolic resin, a compound having one or more, preferably two or more, hydroxyl groups bonded to an aromatic ring such as a benzene ring or a naphthalene ring in one molecule can be used. When combined with an epoxy resin, the phenolic resin reacts with the epoxy resin to harden the resin composition, and is therefore sometimes called a "phenolic hardener." From the viewpoint of heat resistance and water resistance, a phenolic resin having a novolac structure is preferred. From the viewpoint of adhesion, a nitrogen-containing phenolic resin is preferred, and a triazine skeleton-containing phenolic resin is more preferred. Among these, a triazine skeleton-containing phenolic novolac resin is preferred from the viewpoint of highly satisfying heat resistance, water resistance, and adhesion. Specific examples of phenolic resins include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-375", and "SN-395" manufactured by Nippon Steel Chemical & Material Co., Ltd.; and "LA-7052", "LA-7054", "LA-3018", "LA-3018-50P", "LA-1356", "TD2090", and "TD-2090-60M" manufactured by DIC Corporation.

[0067] The amount of the phenolic resin in the resin composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, particularly preferably 1% by mass or more, and is preferably 50% by mass or less, more preferably 40% by mass or less, particularly preferably 30% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the phenolic resin is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0068] The amount of the phenolic resin in the resin composition is preferably 1% by mass or more, more preferably 2% by mass or more, particularly preferably 3% by mass or more, and is preferably 70% by mass or less, more preferably 60% by mass or less, particularly preferably 50% by mass or less, based on 100% by mass of the resin components of the resin composition. When the amount of the phenolic resin is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0069] As the active ester resin, a compound having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, is preferably used. When combined with an epoxy resin, the active ester resin can react with the epoxy resin to harden the resin composition, and is therefore sometimes called an "active ester-based curing agent." The active ester resin is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester resin obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester resin obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.

[0070] Specifically, the active ester resin is preferably a dicyclopentadiene type active ester resin, a naphthalene type active ester resin containing a naphthalene structure, an active ester resin containing an acetylated product of phenol novolac, or an active ester resin containing a benzoylated product of phenol novolac, and more preferably at least one selected from a dicyclopentadiene type active ester resin and a naphthalene type active ester resin. As the dicyclopentadiene type active ester resin, an active ester resin containing a dicyclopentadiene type diphenol structure is preferable.

[0071] Commercially available active ester resins include, for example, active ester resins containing a dicyclopentadiene-type diphenol structure such as "EXB9451", "EXB9460", "EXB9460S", "EXB-8000L", "EXB-8000L-65M", "EXB-8000L-65TM", "HPC-8000L-65TM", "HPC-8000", "HPC-8000-65T", "HPC-8000H", and "HPC-8000H-65TM" (manufactured by DIC Corporation); and active ester resins containing a naphthalene structure such as "HP-B-8151-62T", "EXB-8100L-65T", "EXB-8150-60T", and "EXB-815 Examples of such active ester resins include "EXB9401" (manufactured by DIC Corporation), an active ester resin which is an acetylated product of phenol novolac, such as "DC808" (manufactured by Mitsubishi Chemical Corporation), an active ester resin which is a benzoylated product of phenol novolac, such as "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation), and an active ester resin which contains a styryl group and a naphthalene structure, such as "PC1300-02-65MA" (manufactured by Air Water Corporation).

[0072] The amount of the active ester resin in the resin composition is preferably 1% by mass or more, more preferably 3% by mass or more, particularly preferably 5% by mass or more, and is preferably 40% by mass or less, more preferably 30% by mass or less, particularly preferably 20% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the active ester resin is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0073] The amount of the active ester resin in the resin composition is preferably 1% by mass or more, more preferably 5% by mass or more, particularly preferably 10% by mass or more, and is preferably 80% by mass or less, more preferably 70% by mass or less, particularly preferably 60% by mass or less, based on 100% by mass of the resin components of the resin composition. When the amount of the active ester resin is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0074] As the cyanate resin, a compound having one or more, preferably two or more, cyanate groups in one molecule can be used. When combined with an epoxy resin, the cyanate resin reacts with the epoxy resin to harden the resin composition, and therefore is sometimes called a "cyanate-based curing agent." Examples of the cyanate resin include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanatephenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanatephenyl-1-(methylethylidene))benzene, bis(4-cyanatephenyl)thioether, and bis(4-cyanatephenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate resins include "PT30" and "PT60" (both of which are phenol novolac type multifunctional cyanate resins) manufactured by Lonza Japan, "BA230" and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted into triazine to form a trimer).

[0075] The amount of the cyanate resin in the resin composition is preferably 1% by mass or more, more preferably 3% by mass or more, particularly preferably 5% by mass or more, and is preferably 40% by mass or less, more preferably 30% by mass or less, particularly preferably 20% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the cyanate resin is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0076] The amount of the cyanate resin in the resin composition is preferably 1% by mass or more, more preferably 5% by mass or more, particularly preferably 10% by mass or more, and is preferably 60% by mass or less, more preferably 50% by mass or less, particularly preferably 40% by mass or less, based on 100% by mass of the resin components of the resin composition. When the amount of the cyanate resin is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0077] As the carbodiimide resin, a compound having one or more, preferably two or more, carbodiimide structures in one molecule can be used. When combined with an epoxy resin, the carbodiimide resin reacts with the epoxy resin to harden the resin composition, and is therefore sometimes called a "carbodiimide-based hardener." Specific examples of the carbodiimide resin include aliphatic biscarbodiimides such as tetramethylene-bis(t-butylcarbodiimide) and cyclohexane bis(methylene-t-butylcarbodiimide); aromatic biscarbodiimides such as phenylene-bis(xylylcarbodiimide); aliphatic polycarbodiimides such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), and poly(isophoronecarbodiimide); poly(phenylenecarbodiimide), poly(naphthalenecarbodiimide), and the like. Examples of polycarbodiimides include aromatic polycarbodiimides such as poly(methylenediphenylenecarbodiimide), poly(tolylenecarbodiimide), poly(methyldiisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), poly(diethylphenylenecarbodiimide), poly(triisopropylphenylenecarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(xylylenecarbodiimide), poly(tetramethylxylylenecarbodiimide), poly(methylenediphenylenecarbodiimide), and poly[methylenebis(methylphenylene)carbodiimide]. Commercially available carbodiimide resins include, for example, "Carbodilite V-02B", "Carbodilite V-03", "Carbodilite V-04K", "Carbodilite V-07" and "Carbodilite V-09" manufactured by Nisshinbo Chemical Inc.; and "Stavaxol P", "Stavaxol P400" and "Hi-Kasil 510" manufactured by Rhein Chemie.

[0078] The amount of the carbodiimide resin in the resin composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, particularly preferably 1% by mass or more, and preferably 10% by mass or less, more preferably 8% by mass or less, particularly preferably 5% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the carbodiimide resin is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0079] The amount of the carbodiimide resin in the resin composition is preferably 0.1% by mass or more, more preferably 1% by mass or more, particularly preferably 2% by mass or more, and preferably 20% by mass or less, more preferably 15% by mass or less, particularly preferably 10% by mass or less, based on 100% by mass of the resin components of the resin composition. When the amount of the carbodiimide resin is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0080] As the acid anhydride resin, a compound having one or more, preferably two or more, acid anhydride groups in one molecule can be used. When combined with an epoxy group, the acid anhydride resin reacts with the epoxy resin to harden the resin composition, and is therefore sometimes called an "acid anhydride-based curing agent." Specific examples of the acid anhydride resin include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenone tetracarboxylic anhydride, and the like. Examples of such anhydrides include water, biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resin, which is a copolymer of styrene and maleic acid. Commercially available acid anhydride resins include, for example, "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by New Japan Chemical Co., Ltd.; "YH-306" and "YH-307" manufactured by Mitsubishi Chemical Corporation; "HN-2200" and "HN-5500" manufactured by Hitachi Chemical Co., Ltd.; and "EF-30", "EF-40", "EF-60", and "EF-80" manufactured by Clay Valley Corporation.

[0081] As the amine resin, a compound having one or more, preferably two or more, amino groups in one molecule can be used. When combined with an epoxy group, the amine resin reacts with the epoxy resin to harden the resin composition, and is therefore sometimes called an "amine-based curing agent." Examples of the amine resin include aliphatic amines, polyether amines, alicyclic amines, and aromatic amines, and among these, aromatic amines are preferred. The amine resin is preferably a primary amine or secondary amine, and more preferably a primary amine. Specific examples of amine resins include 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, and 2,2-bis(3-amino-4-hydroxyphenyl)propionate. Pan, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, and the like. Commercially available amine resins include, for example, "SEIKACURE-S" manufactured by Seika Corporation; "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd.; "Epicure W" manufactured by Mitsubishi Chemical Corporation; and "DTDA" manufactured by Sumitomo Seika Chemicals Co., Ltd.

[0082] Benzoxazine resins, when combined with epoxy resins, can react with the epoxy resin to harden the resin composition, and are therefore sometimes called "benzoxazine-based hardeners." Specific examples of benzoxazine resins include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Corporation, "HFB2006M" manufactured by Showa Polymer Co., Ltd., and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.

[0083] Thiol resins, when combined with epoxy resins, can react with the epoxy resin to harden the resin composition, and are therefore sometimes called "thiol-based hardeners." Examples of thiol resins include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.

[0084] The active group equivalent of the curing agent is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 300 g / eq. The active group equivalent is the mass of the curing agent per equivalent of the active group.

[0085] When the number of epoxy groups in the epoxy resin is 1, the number of active groups in the curing agent is preferably 0.1 or more, more preferably 0.2 or more, even more preferably 0.5 or more, and preferably 5.0 or less, more preferably 4.0 or less, and particularly preferably 3.0 or less. The "number of epoxy groups in the epoxy resin" refers to the total value obtained by dividing the mass of the non-volatile components of the epoxy resin present in the resin composition by the epoxy equivalent. The "number of active groups in the curing agent" refers to the total value obtained by dividing the mass of the non-volatile components of the curing agent present in the resin composition by the active group equivalent.

[0086] The amount of the curing agent in the resin composition is preferably 1% by mass or more, more preferably 5% by mass or more, particularly preferably 10% by mass or more, and preferably 50% by mass or less, more preferably 40% by mass or less, particularly preferably 30% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the curing agent is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0087] The amount of the curing agent in the resin composition is preferably 5% by mass or more, more preferably 10% by mass or more, particularly preferably 20% by mass or more, and is preferably 90% by mass or less, more preferably 80% by mass or less, particularly preferably 70% by mass or less, based on 100% by mass of the resin component of the resin composition. When the amount of the curing agent is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0088] A compound having an ethylenically unsaturated bond can be used as the radical polymerizable resin. Thus, the radical polymerizable resin can have a radical polymerizable group containing an ethylenically unsaturated bond. Examples of the radical polymerizable group include unsaturated hydrocarbon groups such as vinyl group, allyl group, 1-propenyl group, 3-cyclohexenyl group, 3-cyclopentenyl group, 2-vinylphenyl group, 3-vinylphenyl group, and 4-vinylphenyl group; and α,β-unsaturated carbonyl groups such as acryloyl group, methacryloyl group, and maleimide group (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl group). The number of radical polymerizable groups contained in one molecule of the radical polymerizable resin may be one, but is preferably two or more. One type of radical polymerizable resin may be used alone, or two or more types may be used in combination. Preferred radical polymerizable resins include (meth)acrylic resins, styryl resins, propenyl resins, and maleimide resins.

[0089] The (meth)acrylic resin may be a compound having one or more, preferably two or more, (meth)acryloyl groups in one molecule. The (meth)acrylic resin may be a monomer or an oligomer. The term "(meth)acryloyl group" may include an acryloyl group, a methacryloyl group, and a combination thereof. Examples of the (meth)acrylic resin include cyclohexane-1,4-dimethanol di(meth)acrylate, cyclohexane-1,3-dimethanol di(meth)acrylate, tricyclodecane dimethanol di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,8-octanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, and the like. Di(meth)acrylate, 1,10-decanediol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, trimethylolethane tri(meth)acrylate, glycerin tri(meth)acrylate, pentaerythritol tetra(meth)acrylate, and other low molecular weight (molecular weight less than 1000) aliphatic (meth)acrylic acid ester compounds; dioxane glycol di(meth)acrylate, 3,6-dioxa-1,8-octanediol di(meth)acrylate, Examples of the ether-containing (meth)acrylic acid ester compounds include low molecular weight (molecular weight less than 1000) ether-containing (meth)acrylic acid ester compounds such as acrylate, 3,6,9-trioxaundecane-1,11-diol di(meth)acrylate, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, 9,9-bis[4-(2-acryloyloxyethoxy)phenyl]fluorene, ethoxylated bisphenol A di(meth)acrylate, and propoxylated bisphenol A di(meth)acrylate; low molecular weight (molecular weight less than 1000) isocyanurate-containing (meth)acrylic acid ester compounds such as tris(3-hydroxypropyl)isocyanurate tri(meth)acrylate, tris(2-hydroxyethyl)isocyanurate tri(meth)acrylate, and ethoxylated isocyanuric acid tri(meth)acrylate; and high molecular weight (molecular weight 1000 or more) acrylic acid ester compounds such as (meth)acrylic-modified polyphenylene ether resin.Examples of commercially available (meth)acrylic resins include "A-DOG" manufactured by Shin-Nakamura Chemical Co., Ltd.; "DCP" and "DCP-A" manufactured by Kyoeisha Chemical Co., Ltd.; "NPDGA", "FM-400", "R-604", "R-684", "R-687", "THE-330", "PET-30", and "DPHA" manufactured by Nippon Kayaku Co., Ltd.; and "SA9000" and "SA9000-111" manufactured by SABIC Innovative Plastics.

[0090] The styryl resin may be a compound having one or more, preferably two or more, styryl groups or vinylphenyl groups in one molecule. The styryl resin may be a monomer or an oligomer. Examples of the styryl resin include low molecular weight (molecular weight less than 1000) styrene-based compounds such as divinylbenzene, 2,4-divinyltoluene, 2,6-divinylnaphthalene, 1,4-divinylnaphthalene, 4,4'-divinylbiphenyl, 1,2-bis(4-vinylphenyl)ethane, 2,2-bis(4-vinylphenyl)propane, and bis(4-vinylphenyl)ether; and high molecular weight (molecular weight 1000 or more) styrene-based compounds such as vinylbenzyl-modified polyphenylene ether resin and styrene-divinylbenzene copolymer. Examples of commercially available styryl resins include "OPE-2St", "OPE-2St 1200", and "OPE-2St 2200" manufactured by Mitsubishi Gas Chemical Company, Inc.

[0091] The propenyl resin may be a compound having one or more, preferably two or more, propenyl groups in one molecule. The propenyl resin may be a monomer or an oligomer. The propenyl group may include a 1-propenyl group, a 2-propenyl group (i.e., an allyl group), and a combination thereof. Examples of the propenyl resin include aromatic carboxylic acid allyl ester compounds such as diallyl diphenate, triallyl trimellitate, diallyl phthalate, diallyl isophthalate, diallyl terephthalate, diallyl 2,6-naphthalenedicarboxylate, and diallyl 2,3-naphthalenecarboxylate; isocyanuric acid allyl ester compounds such as 1,3,5-triallyl isocyanurate and 1,3-diallyl-5-glycidyl isocyanurate; epoxy-containing aromatic allyl compounds such as 2,2-bis[3-allyl-4-(glycidyloxy)phenyl]propane; benzoxazine-containing aromatic allyl compounds such as bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane; ether-containing aromatic allyl compounds such as 1,3,5-triallyl ether benzene; and allyl silane compounds such as diallyl diphenyl silane. Examples of commercially available propenyl resins include "TAIC" (1,3,5-triallyl isocyanurate) manufactured by Nippon Kasei Chemical Industry Co., Ltd., "DAD" (diallyl diphenate) manufactured by Nisshoku Techno Fine Chemical Co., Ltd., "TRIAM-705" (triallyl trimellitate) manufactured by Wako Pure Chemical Industries, Ltd., "DAND" (2,3-diallyl naphthalene carboxylate) manufactured by Nippon Distillation Industry Co., Ltd., "ALP-d" (bis[3-allyl-4-(3,4-dihydro-2H-1,3-benzoxazin-3-yl)phenyl]methane) manufactured by Shikoku Kasei Corporation, "RE-810NM" (2,2-bis[3-allyl-4-(glycidyloxy)phenyl]propane) manufactured by Nippon Kayaku Co., Ltd., and "DA-MGIC" (1,3-diallyl-5-glycidyl isocyanurate) manufactured by Shikoku Kasei Corporation. In addition, the propenyl resin may be a resin containing a hydroxyl group bonded to an aromatic ring, for example, a resin represented by the following formula (b1): Such a propenyl resin containing a hydroxyl group bonded to an aromatic ring can function not only as a radical polymerizable resin but also as a phenol-based curing agent.

[0092] [ka]

[0093] The maleimide resin may be a compound having one or more, preferably two or more, maleimide groups (2,5-dihydro-2,5-dioxo-1H-pyrrol-1-yl groups) in one molecule. The maleimide resin may be a monomer or an oligomer. Examples of commercially available maleimide resins include maleimide resins containing an aliphatic skeleton having 36 carbon atoms derived from dimer diamine, such as "BMI-3000J", "BMI-5000", "BMI-1400", "BMI-1500", "BMI-1700", and "BMI-689" (all manufactured by DigiCner Molecules); maleimide resins containing an indane skeleton, as described in the Japan Institute of Invention and Innovation Disclosure Technical Bulletin No. 2020-500211; and maleimide resins containing an aromatic ring skeleton directly bonded to the nitrogen atom of the maleimide group, such as "MIR-3000-70MT" (manufactured by Nippon Kayaku Co., Ltd.), "BMI-4000" (manufactured by Daiwa Kasei Co., Ltd.), and "BMI-80" (manufactured by Keiai Kasei Co., Ltd.).

[0094] The ethylenically unsaturated bond equivalent of the radical polymerizable resin is preferably 20 g / eq. to 3000 g / eq., more preferably 50 g / eq. to 2500 g / eq., further preferably 70 g / eq. to 2000 g / eq., and particularly preferably 90 g / eq. to 1500 g / eq. The ethylenically unsaturated bond equivalent represents the mass of the radical polymerizable resin per equivalent of the ethylenically unsaturated bond.

[0095] The weight average molecular weight (Mw) of the radical polymerizable resin is preferably 40000 or less, more preferably 10000 or less, further preferably 5000 or less, and particularly preferably 3000 or less. The lower limit is not particularly limited, but may be, for example, 150 or more. The weight average molecular weight of the radical polymerizable resin can be measured as a polystyrene-equivalent value by gel permeation chromatography (GPC).

[0096] The amount of the radical polymerizable resin in the resin composition is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, particularly preferably 0.5% by mass or more, and preferably 10% by mass or less, more preferably 5% by mass or less, particularly preferably 1% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the radical polymerizable resin is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0097] The amount of the radical polymerizable resin in the resin composition is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, particularly preferably 1% by mass or more, and preferably 20% by mass or less, more preferably 10% by mass or less, particularly preferably 5% by mass or less, based on 100% by mass of the resin components of the resin composition. When the amount of the radical polymerizable resin is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0098] Among the above, it is preferable that the (B) curable resin contains one or more selected from the group consisting of epoxy resin, phenol resin, active ester resin, cyanate resin, (meth)acrylic resin, styryl resin, propenyl resin, and maleimide resin. At this time, the total amount of the resins selected from the above group is preferably 50% by mass or more, more preferably 70% by mass or more, particularly preferably 90% by mass or more, and usually 100% by mass or less, based on 100% by mass of the (B) curable resin. When the (B) curable resin contains such a preferable resin, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0099] The amount of the (B) curable resin in the resin composition is preferably 5% by mass or more, more preferably 10% by mass or more, particularly preferably 20% by mass or more, and is preferably 80% by mass or less, more preferably 60% by mass or less, particularly preferably 50% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the (B) curable resin is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0100] The amount of the (B) curable resin in the resin composition is preferably 50% by mass or more, more preferably 60% by mass or more, particularly preferably 70% by mass or more, and is preferably 98% by mass or less, more preferably 96% by mass or less, particularly preferably 94% by mass or less, based on 100% by mass of the resin components of the resin composition. When the amount of the (B) curable resin is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0101] <(C) Inorganic Filler According to the First Embodiment> The resin composition according to the first embodiment of the present invention may further contain an inorganic filler (C) as an optional component. The inorganic filler (C) as the component (C) does not include those corresponding to the above-mentioned components (A) and (B). The inorganic filler (C) is usually contained in the resin composition in the form of particles.

[0102] (C) An inorganic compound is used as the material of the inorganic filler. (C) Examples of the material of the inorganic filler include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica and alumina are preferred, and silica is particularly preferred. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, spherical silica is preferred as the silica. The (C) inorganic filler may be used alone or in combination of two or more kinds.

[0103] (C) Inorganic fillers can be classified into hollow inorganic fillers having voids inside and solid inorganic fillers having no voids inside. (C) Inorganic fillers may be used only with hollow inorganic fillers, only with solid inorganic fillers, or in combination with hollow inorganic fillers and solid inorganic fillers. When using hollow inorganic fillers, the dielectric constant of the cured product of the resin composition can usually be reduced.

[0104] Since the hollow inorganic filler has pores, it usually has a porosity of more than 0 volume%. From the viewpoint of lowering the relative dielectric constant of the insulating layer containing the cured product of the resin composition, the porosity of the hollow inorganic filler is preferably 5 volume% or more, more preferably 10 volume% or more, and particularly preferably 15 volume% or more. In addition, from the viewpoint of the mechanical strength of the cured product of the resin composition, the porosity of the hollow inorganic filler is preferably 95 volume% or less, more preferably 90 volume% or less, and particularly preferably 85 volume% or less.

[0105] The porosity P (volume %) of a particle is defined as the volume ratio of the total volume of one or more pores present inside the particle to the total volume of the particle based on the outer surface of the particle (total volume of pores / volume of particle). This porosity P is calculated by multiplying the measured value of the actual density D of the particle by the volume ratio of the particle. M (g / cm 3 ), and the theoretical density of the material that forms the particle D T (g / cm 3 ) can be calculated using the following formula (X1).

[0106]

number

[0107] The hollow inorganic filler may be produced, for example, by the methods described in Japanese Patent Nos. 5,940,188 and 5,864,299 or methods equivalent thereto.

[0108] (C) Commercially available inorganic fillers include, for example, "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" manufactured by Tokuyama Corporation; "Cellfiers" manufactured by Taiheiyo Cement Corporation; and "Sferique" manufactured by JGC Catalysts and Chemicals Co., Ltd.

[0109] From the viewpoint of significantly obtaining the desired effects of the present invention, the average particle size of the (C) inorganic filler is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 3 μm or less.

[0110] (C) The average particle size of the inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is prepared on a volume basis using a laser diffraction / scattering particle size distribution measuring device, and the median diameter is used as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing the mixture by ultrasonic waves for 10 minutes. The measurement sample can be measured by using a laser diffraction particle size distribution measuring device with blue and red light wavelengths as the light source, measuring the particle size distribution of the inorganic filler on a volume basis using a flow cell method, and calculating the average particle size as the median diameter from the particle size distribution obtained. An example of a laser diffraction particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.

[0111] The specific surface area of ​​the (C) inorganic filler is preferably 0.1 m from the viewpoint of significantly obtaining the desired effects of the present invention. 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 / g or more, preferably 100m 2 / g or less, more preferably 70m 2 / g or less, more preferably 50m 2 / g or less, particularly preferably 40m 2 The specific surface area of ​​the inorganic filler can be measured by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountech Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.

[0112] (C) The inorganic filler is preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. Examples of the surface treatment agent include fluorine-containing silane coupling agents, aminosilane coupling agents, epoxysilane coupling agents, mercaptosilane coupling agents, silane coupling agents, alkoxysilanes, organosilazane compounds, titanate coupling agents, etc. The surface treatment agent may be used alone or in any combination of two or more.

[0113] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).

[0114] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment with the surface treatment agent is preferably within a specific range. Specifically, 100% by mass of the inorganic filler is preferably surface-treated with 0.2% to 5% by mass of the surface treatment agent, more preferably with 0.2% to 3% by mass of the surface treatment agent, and even more preferably with 0.3% to 2% by mass of the surface treatment agent.

[0115] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of ​​the inorganic filler is set to 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of preventing an increase in the melt viscosity of the resin composition, it is more preferable that the content is 1.0 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:

[0116] (C) The amount of carbon per unit surface area of ​​the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of ​​the inorganic filler can be measured using a carbon analyzer. As the carbon analyzer, the "EMIA-320V" manufactured by Horiba, Ltd., or the like can be used.

[0117] The amount of the inorganic filler (C) in the resin composition may be 0% by mass or more, and is preferably 10% by mass or more, more preferably 20% by mass or more, particularly preferably 30% by mass or more, and is preferably 94% by mass or less, more preferably 90% by mass or less, particularly preferably 80% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the inorganic filler (C) is within the above range, the dielectric tangent, crack resistance, and blister resistance of the insulating layer can be effectively improved, and furthermore, the relative dielectric constant of the insulating layer can usually be reduced.

[0118] <(D) Curing Accelerator According to the First Embodiment> The resin composition according to the first embodiment of the present invention may further contain a curing accelerator (D) as an optional component. The curing accelerator (D) as the component (D) does not include those corresponding to the above-mentioned components (A) to (C). The curing accelerator (D) functions as a curing catalyst that accelerates the curing of the curable resin (B).

[0119] As the (D) curing accelerator, an appropriate one can be used depending on the type of the (B) curable resin. For example, when the (B) curable resin contains an epoxy resin, examples of the (D) curing accelerator that can accelerate the curing of the epoxy resin include phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, imidazole-based curing accelerators, metal-based curing accelerators, and amine-based curing accelerators. The (D) curing accelerators may be used alone or in combination of two or more.

[0120] Examples of the phosphorus-based curing accelerator include aliphatic phosphonium salts such as tetrabutyl phosphonium bromide, tetrabutyl phosphonium chloride, tetrabutyl phosphonium acetate, tetrabutyl phosphonium decanoate, tetrabutyl phosphonium laurate, bis(tetrabutyl phosphonium)pyromellitate, tetrabutyl phosphonium hydrogenhexahydrophthalate, tetrabutyl phosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butyldimethylphosphonium tetraphenylborate; methyl triphenyl phosphonium bromide, ethyl triphenyl phosphonium bromide, propyl triphenyl phosphonium bromide, butyl triphenyl phosphonium bromide, benzyl triphenyl phosphonium chloride, tetraphenyl phosphonium bromide, p-tolyl triphenyl phosphonium tetra-p-tolylborate, tetraphenyl phosphonium bromide, and the like. aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples of aromatic phosphines include tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether.

[0121] Examples of the urea-based curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. aromatic dimethylureas such as butylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluene bisdimethylurea].

[0122] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide.

[0123] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-methylimidazole. Phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct , 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, 2-phenylimidazoline, and other imidazole compounds and adducts of imidazole compounds and epoxy resins. Commercially available imidazole curing accelerators include, for example, "1B2PZ", "2E4MZ", "2MZA-PW", "2MZ-OK", "2MA-OK", "2MA-OK-PW", "2PHZ", "2PHZ-PW", "Cl1Z", "Cl1Z-CN", "Cl1Z-CNS", and "C11Z-A" manufactured by Shikoku Chemical Industry Co., Ltd.; and "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0124] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(III) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(III) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0125] Examples of the amine-based curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, 1,8-diazabicyclo(5,4,0)-undecene, etc. Commercially available amine-based curing accelerators may be used, such as "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0126] The amount of the (D) curing accelerator in the resin composition may be 0% by mass or more than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, and particularly preferably 0.05% by mass or more, and is preferably 1.0% by mass or less, more preferably 0.5% by mass or less, and particularly preferably 0.2% by mass or less, relative to 100% by mass of the non-volatile components of the resin composition.

[0127] The amount of the (D) curing accelerator in the resin composition may be 0 mass% or more than 0 mass%, and is preferably 0.01 mass% or more, more preferably 0.05 mass% or more, and particularly preferably 0.1 mass% or more, and is preferably 2.0 mass% or less, more preferably 1.0 mass% or less, and particularly preferably 0.5 mass% or less, relative to 100 mass% of the resin component of the resin composition.

[0128] <Thermoplastic resin (E) according to the first embodiment> The resin composition according to the first embodiment of the present invention may further contain a thermoplastic resin (E) as an optional component. The thermoplastic resin (E) as the component (E) does not include those corresponding to the above-mentioned components (A) to (D).

[0129] Examples of the (E) thermoplastic resin include phenoxy resin, polyimide resin, polyvinyl acetal resin, polyolefin resin, polybutadiene resin, polyamideimide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polycarbonate resin, polyetheretherketone resin, polyester resin, etc. The (E) thermoplastic resin may be used alone or in combination of two or more kinds.

[0130] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group. Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton); "FX280" and "FX293" manufactured by Nippon Steel & Sumikin Chemical Co., Ltd.; "YL7500BH30", "YX6954BH30", "YX7553", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", "YL7482", and "YL7891BH30" manufactured by Mitsubishi Chemical Corporation.

[0131] Specific examples of polyimide resins include "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., and "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd.

[0132] Examples of polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred.Specific examples of polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd.; S-LEC BH series, BX series (e.g. BX-5Z), KS series (e.g. KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.

[0133] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymer.

[0134] Examples of polybutadiene resins include hydrogenated polybutadiene skeleton-containing resins, hydroxy group-containing polybutadiene resins, phenolic hydroxy group-containing polybutadiene resins, carboxy group-containing polybutadiene resins, acid anhydride group-containing polybutadiene resins, epoxy group-containing polybutadiene resins, isocyanate group-containing polybutadiene resins, urethane group-containing polybutadiene resins, polyphenylene ether-polybutadiene resins, and the like.

[0135] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.

[0136] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.

[0137] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.

[0138] A specific example of the polyphenylene ether resin is NORYL SA90 manufactured by SABIC, etc. A specific example of the polyetherimide resin is ULTEM manufactured by GE, etc.

[0139] Examples of polycarbonate resins include hydroxyl group-containing carbonate resins, phenolic hydroxyl group-containing carbonate resins, carboxyl group-containing carbonate resins, acid anhydride group-containing carbonate resins, isocyanate group-containing carbonate resins, and urethane group-containing carbonate resins. Specific examples of polycarbonate resins include "FPC0220" manufactured by Mitsubishi Gas Chemical Co., Ltd., "T6002" and "T6001" (polycarbonate diol) manufactured by Asahi Kasei Chemicals Corporation, and "C-1090", "C-2090", and "C-3090" (polycarbonate diol) manufactured by Kuraray Co., Ltd. Specific examples of polyether ether ketone resins include "Sumiploy K" manufactured by Sumitomo Chemical Co., Ltd.

[0140] Examples of polyester resins include polyethylene terephthalate resins, polyethylene naphthalate resins, polybutylene terephthalate resins, polybutylene naphthalate resins, polytrimethylene terephthalate resins, polytrimethylene naphthalate resins, and polycyclohexane dimethyl terephthalate resins.

[0141] The weight average molecular weight (Mw) of the (E) thermoplastic resin is preferably greater than 5,000, more preferably at least 8,000, even more preferably at least 10,000, particularly preferably at least 20,000, and is preferably at most 100,000, more preferably at most 70,000, even more preferably at most 60,000, particularly preferably at most 50,000. The weight average molecular weight of the (E) thermoplastic resin can be measured as a polystyrene-equivalent value by gel permeation chromatography (GPC).

[0142] The amount of the (E) thermoplastic resin in the resin composition may be 0% by mass or more than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and particularly preferably 0.5% by mass or more, and is preferably 20% by mass or less, more preferably 10% by mass or less, and particularly preferably 5% by mass or less, based on 100% by mass of the non-volatile components of the resin composition.

[0143] The amount of the (E) thermoplastic resin in the resin composition may be 0% by mass or more than 0% by mass, and is preferably 0.1% by mass or more, more preferably 1% by mass or more, and particularly preferably 2% by mass or more, and is preferably 30% by mass or less, more preferably 20% by mass or less, and particularly preferably 10% by mass or less, relative to 100% by mass of the resin components of the resin composition.

[0144] <(F) Optional Additive According to the First Embodiment> The resin composition according to the first embodiment of the present invention may further contain an optional additive (F) as an optional non-volatile component. The optional additive (F) as the component (F) does not include those corresponding to the above-mentioned components (A) to (E). The optional additive (F) may be, for example, a radical polymerization initiator such as a peroxide radical polymerization initiator or an azo radical polymerization initiator; an organometallic compound such as an organocopper compound, an organozinc compound, or an organocobalt compound; a colorant such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, or carbon black; a polymerization inhibitor such as hydroquinone, catechol, pyrogallol, or phenothiazine; a leveling agent such as a silicone leveling agent or an acrylic polymer leveling agent; a thickener such as bentone or montmorillonite; an antifoaming agent such as a silicone antifoaming agent, an acrylic antifoaming agent, a fluorine antifoaming agent, or a vinyl resin antifoaming agent; an ultraviolet absorbing agent such as a benzotriazole ultraviolet absorbing agent; an adhesion improver such as urea silane; a triazole adhesion imparting agent, a tetrazo Examples of the additives include adhesion promoters such as phenol-based adhesion promoters and triazine-based adhesion promoters; antioxidants such as hindered phenol-based antioxidants; fluorescent brighteners such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; flame retardants such as phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, red phosphorus), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, and inorganic flame retardants (e.g., antimony trioxide); dispersants such as phosphate ester-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers. (F) Optional additives may be used alone or in combination of two or more.

[0145] <Solvent (G) according to the first embodiment> The resin composition according to the first embodiment of the present invention may further contain a (G) solvent as an optional volatile component in combination with the non-volatile components such as the above-mentioned components (A) to (F). As the (G) solvent, an organic solvent is usually used. Examples of the organic solvent include ketone-based solvents such as acetone, methyl ethyl ketone, methyl isobutyl ketone, and cyclohexanone; ester-based solvents such as methyl acetate, ethyl acetate, butyl acetate, isobutyl acetate, isoamyl acetate, methyl propionate, ethyl propionate, and γ-butyrolactone; ether-based solvents such as tetrahydropyran, tetrahydrofuran, 1,4-dioxane, diethyl ether, diisopropyl ether, dibutyl ether, diphenyl ether, and anisole; alcohol-based solvents such as methanol, ethanol, propanol, butanol, and ethylene glycol; 2-ethoxyethyl acetate, propylene glycol monomethyl ether acetate, diethylene glycol monoethyl ether acetate, ethyl diglycol acetate, γ-butyrolactone, and methyl methoxypropionate. Examples of the solvent include ether ester solvents such as ethyl acetate, ester alcohol solvents such as methyl lactate, ethyl lactate, and methyl 2-hydroxyisobutyrate, ether alcohol solvents such as 2-methoxypropanol, 2-methoxyethanol, 2-ethoxyethanol, propylene glycol monomethyl ether, and diethylene glycol monobutyl ether (butylcarbitol), amide solvents such as N,N-dimethylformamide, N,N-dimethylacetamide, and N-methyl-2-pyrrolidone, sulfoxide solvents such as dimethyl sulfoxide, nitrile solvents such as acetonitrile and propionitrile, aliphatic hydrocarbon solvents such as hexane, cyclopentane, cyclohexane, and methylcyclohexane, and aromatic hydrocarbon solvents such as benzene, toluene, xylene, ethylbenzene, and trimethylbenzene. The (G) solvent may be used alone or in combination of two or more.

[0146] The amount of (G) solvent is not particularly limited, but when all components in the resin composition are taken as 100 mass%, it can be, for example, 60 mass% or less, 40 mass% or less, 30 mass% or less, 20 mass% or less, 15 mass% or less, 10 mass% or less, or it can be 0 mass%.

[0147] <Method of producing resin composition according to the first embodiment> The resin composition according to the first embodiment of the present invention can be produced, for example, by mixing components that can be contained in the resin composition. The above-mentioned components may be mixed in part or in whole simultaneously, or may be mixed in order. In the process of mixing each component, the temperature may be appropriately set, and thus heating and / or cooling may be performed temporarily or throughout. In addition, stirring or shaking may be performed in the process of mixing each component.

[0148] <Characteristics of the resin composition according to the first embodiment> A cured product is obtained by curing the resin composition according to the first embodiment of the present invention. During the above-mentioned effect, heat is usually applied to the resin composition. Therefore, among the components contained in the resin composition, volatile components such as (G) solvent can usually be volatilized by heat during curing, but non-volatile components such as components (A) to (F) do not volatilize by heat during curing. Therefore, the cured product of the resin composition can contain the non-volatile components of the resin composition or their reaction products.

[0149] The cured product of the resin composition according to the first embodiment of the present invention can have a low dielectric loss tangent. Therefore, when an insulating layer is formed with this cured product, an insulating layer with a low dielectric loss tangent can be obtained. The dielectric loss tangent of the cured product of the resin composition is preferably 0.040 or less, more preferably 0.030 or less, and particularly preferably 0.020 or less. There is no particular restriction on the lower limit, and it can be, for example, 0.0001 or more. The dielectric loss tangent of the cured product can be measured by the method described in <Test Example I-1: Measurement of relative dielectric constant (Dk) and dielectric loss tangent (Df)> in the examples described later.

[0150] The cured product of the resin composition according to the first embodiment of the present invention has excellent crack resistance. Therefore, when an insulating layer is formed from this cured product, an insulating layer having excellent crack resistance can be obtained. For example, when crack resistance is evaluated by the method described in <Test Example I-2: Evaluation of Crack Resistance> in the examples described later, the yield can be preferably 40% or more, more preferably 60% or more, and particularly preferably 80% or more. Usually, the higher the yield value, the more excellent the crack resistance.

[0151] The cured product of the resin composition according to the first embodiment of the present invention has excellent blister resistance. Therefore, when an insulating layer is formed using this cured product, blisters during reflow can be suppressed. For example, when evaluation is performed using the method described in <Test Example I-3: Evaluation of Blister Resistance> in the examples described later, abnormalities such as swelling of the conductor layer formed on the insulating layer containing the cured product of the resin composition can be suppressed.

[0152] The cured product of the resin composition according to the first embodiment of the present invention can usually have a low relative dielectric constant. Therefore, when an insulating layer is formed with this cured product, an insulating layer with a low relative dielectric constant can be obtained. The relative dielectric constant of the cured product of the resin composition is preferably 4.0 or less, more preferably 3.8 or less, and particularly preferably 3.5 or less. There is no particular restriction on the lower limit, and it can be, for example, 0.1 or more. The dielectric loss tangent of the cured product can be measured by the method described in <Test Example I-1: Measurement of relative dielectric constant (Dk) and dielectric loss tangent (Df)> in the examples described later.

[0153] <Outline of Resin Composition According to Second Embodiment> The resin composition according to the second embodiment of the present invention includes a combination of an organic filler (A) and a curable resin (B). The organic filler (A) includes a polymer (1) containing a repeating unit represented by formula (1). The organic filler (A) has an average particle size within a specific range.

[0154] [ka] (In formula (1), R a each independently represents a hydrogen atom or a monovalent saturated hydrocarbon group, R b represents a hydrogen atom or a monovalent hydrocarbon group which may have a substituent.

[0155] According to the resin composition of the second embodiment, an insulating layer having excellent crack resistance, temperature stability of the dielectric loss tangent at high temperatures, and insulation reliability can be obtained. In addition, this insulating layer can usually have low dielectric properties such as a relative dielectric constant and a dielectric loss tangent.

[0156] <(A) Organic Filler According to Second Embodiment> The resin composition according to the second embodiment of the present invention contains an organic filler (A) as component (A). This organic filler (A) is present in the resin composition in a particulate form, and is usually included in the cured product while maintaining its particulate form. The organic filler (A) may be used alone or in combination of two or more types. The organic filler (A) according to the second embodiment may be the same as the organic filler (A) described in the first embodiment. Therefore, the range of the organic filler (A) according to the second embodiment may be the same as the range of the organic filler (A) according to the first embodiment.

[0157] Therefore, the polymer (1) in the second embodiment may be the same as the polymer (1) described in the first embodiment. The amount of the polymer (1) contained in the (A) organic filler according to the second embodiment may be the same as the amount of the polymer (1) contained in the (A) organic filler according to the first embodiment. The type and amount of any component that the (A) organic filler according to the second embodiment may be the same as the type and amount of any component that the (A) organic filler according to the first embodiment may contain. The (A) organic filler according to the second embodiment may contain a shell part and a core part, etc. The shell part and the core part that the (A) organic filler according to the second embodiment may be the same as the core part and the shell part that the (A) organic filler according to the first embodiment may contain. The average particle size range of the (A) organic filler according to the second embodiment may be the same as the average particle size range of the (A) organic filler according to the first embodiment. The (A) organic filler according to the second embodiment may be treated with a surface treatment agent. The surface treatment agent for the organic filler (A) according to the second embodiment may be the same as the surface treatment agent for the organic filler (A) according to the first embodiment.

[0158] The organic filler (A) containing the polymer (1) can usually exert the effect of relaxing stress in the cured product of the resin composition, and therefore can improve the crack resistance of the cured product. In addition, cured products containing an organic filler containing the polymer (1) have traditionally tended to be inferior in temperature stability of the dielectric tangent at high temperatures and insulation reliability. In contrast, in the second embodiment of the present invention, the organic filler (A) having an average particle size in a specific range is used, and thus the temperature stability of the dielectric tangent at high temperatures and insulation reliability can be improved. Therefore, by forming an insulating layer using the cured product of the resin composition according to the second embodiment, an insulating layer excellent in crack resistance, temperature stability of the dielectric tangent at high temperatures, and insulation reliability can be obtained. When the average particle size of the organic filler (A) is controlled, the inventors first discovered that the temperature stability of the dielectric tangent at high temperatures and insulation reliability can be improved while maintaining high crack resistance, and this effect is unexpected from the perspective of conventional technical common sense. In addition, the cured product can usually have low polarity, and therefore the dielectric properties such as the dielectric tangent can be reduced.

[0159] The range of the amount of the organic filler (A) contained in the resin composition according to the second embodiment may be the same as or different from the range of the amount of the organic filler (A) contained in the resin composition according to the first embodiment.

[0160] In a particularly desirable embodiment, the amount of the (A) organic filler contained in the resin composition according to the second embodiment of the present invention is preferably 0.2% by mass or more, more preferably 0.5% by mass or more, particularly preferably 1% by mass or more, and preferably 5% by mass or less, more preferably 4.5% by mass or less, particularly preferably 4% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the (A) organic filler is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric loss tangent at high temperatures, and the insulating reliability can be particularly improved, and furthermore, the relative dielectric constant and dielectric loss tangent can usually be reduced.

[0161] In a particularly desirable embodiment, the amount of the (A) organic filler contained in the resin composition according to the second embodiment of the present invention is preferably 0.5% by mass or more, more preferably 1% by mass or more, particularly preferably 3% by mass or more, and preferably 25% by mass or less, more preferably 20% by mass or less, particularly preferably 15% by mass or less, based on 100% by mass of the resin components of the resin composition. As described above, the resin components of the resin composition refer to the non-volatile components of the resin composition excluding the (C) inorganic filler. When the amount of the (A) organic filler is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric loss tangent at high temperatures, and the insulating reliability can be particularly improved, and moreover, the relative dielectric constant and the dielectric loss tangent can usually be reduced.

[0162] <(B) Curable resin according to the second embodiment> The resin composition according to the second embodiment of the present invention contains a (B) curable resin as the (B) component. The (B) curable resin does not include those corresponding to the above-mentioned (A) component. The (B) curable resin may be used alone or in combination of two or more types. The (B) curable resin according to the second embodiment may be the same as the (B) curable resin described in the first embodiment. Therefore, the range of the (B) curable resin according to the second embodiment may be the same as the range of the (B) curable resin according to the first embodiment.

[0163] Therefore, the curable resin (B) according to the second embodiment may contain an epoxy resin. The epoxy resin according to the second embodiment may be the same as the epoxy resin according to the first embodiment. The range of the amount of the epoxy resin contained in the resin composition according to the second embodiment may be the same as or different from the range of the amount of the epoxy resin contained in the resin composition according to the first embodiment.

[0164] In a particularly desirable embodiment, the amount of the epoxy resin in the resin composition according to the second embodiment is preferably 1% by mass or more, more preferably 2% by mass or more, particularly preferably 5% by mass or more, and is preferably 40% by mass or less, more preferably 30% by mass or less, particularly preferably 20% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the epoxy resin is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric loss tangent at high temperatures, and the insulating reliability can be particularly improved, and furthermore, the relative dielectric constant and dielectric loss tangent can usually be reduced.

[0165] In a particularly desirable embodiment, the amount of the epoxy resin in the resin composition according to the second embodiment is preferably 5% by mass or more, more preferably 10% by mass or more, particularly preferably 20% by mass or more, and preferably 60% by mass or less, more preferably 50% by mass or less, particularly preferably 40% by mass or less, based on 100% by mass of the resin components of the resin composition. When the amount of the epoxy resin is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric loss tangent at high temperatures, and the insulating reliability can be particularly improved, and furthermore, the relative dielectric constant and dielectric loss tangent can usually be reduced.

[0166] The (B) curable resin according to the second embodiment may contain a phenolic resin. The phenolic resin according to the second embodiment may be the same as the phenolic resin according to the first embodiment. The range of the amount of the phenolic resin contained in the resin composition according to the second embodiment may be the same as or different from the range of the amount of the phenolic resin contained in the resin composition according to the first embodiment.

[0167] In a particularly desirable embodiment, the amount of the phenolic resin in the resin composition according to the second embodiment is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, particularly preferably 1% by mass or more, and preferably 30% by mass or less, more preferably 20% by mass or less, particularly preferably 10% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the phenolic resin is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric loss tangent at high temperatures, and the insulating reliability can be particularly improved, and furthermore, the relative dielectric constant and dielectric loss tangent can usually be reduced.

[0168] In a particularly desirable embodiment, the amount of the phenolic resin in the resin composition according to the second embodiment is preferably 1% by mass or more, more preferably 2% by mass or more, particularly preferably 3% by mass or more, and preferably 40% by mass or less, more preferably 30% by mass or less, particularly preferably 20% by mass or less, based on 100% by mass of the resin components of the resin composition. When the amount of the phenolic resin is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric loss tangent at high temperatures, and the insulating reliability can be particularly improved, and furthermore, the relative dielectric constant and dielectric loss tangent can usually be reduced.

[0169] Furthermore, the (B) curable resin according to the second embodiment may contain an active ester resin. The active ester resin according to the second embodiment may be the same as the active ester resin according to the first embodiment. The range of the amount of the active ester resin contained in the resin composition according to the second embodiment may be the same as or different from the range of the amount of the active ester resin contained in the resin composition according to the first embodiment.

[0170] In a particularly desirable embodiment, the amount of the active ester resin in the resin composition according to the second embodiment is preferably 1% by mass or more, more preferably 5% by mass or more, particularly preferably 10% by mass or more, and preferably 40% by mass or less, more preferably 30% by mass or less, particularly preferably 20% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the active ester resin is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric loss tangent at high temperatures, and the insulating reliability can be particularly improved, and furthermore, the relative dielectric constant and dielectric loss tangent can usually be reduced.

[0171] In a particularly desirable embodiment, the amount of the active ester resin in the resin composition according to the second embodiment is preferably 10% by mass or more, more preferably 20% by mass or more, particularly preferably 30% by mass or more, and preferably 80% by mass or less, more preferably 70% by mass or less, particularly preferably 60% by mass or less, based on 100% by mass of the resin components of the resin composition. When the amount of the active ester resin is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric loss tangent at high temperatures, and the insulating reliability can be particularly improved, and furthermore, the relative dielectric constant and dielectric loss tangent can usually be reduced.

[0172] In addition, the (B) curable resin according to the second embodiment may contain a cyanate resin. The cyanate resin according to the second embodiment may be the same as the cyanate resin according to the first embodiment. The range of the amount of the cyanate resin contained in the resin composition according to the second embodiment may be the same as or different from the range of the amount of the cyanate resin contained in the resin composition according to the first embodiment.

[0173] Furthermore, the (B) curable resin according to the second embodiment may contain a carbodiimide resin. The carbodiimide resin according to the second embodiment may be the same as the carbodiimide resin according to the first embodiment. The range of the amount of the carbodiimide resin contained in the resin composition according to the second embodiment may be the same as or different from the range of the amount of the carbodiimide resin contained in the resin composition according to the first embodiment.

[0174] In a particularly desirable embodiment, the amount of the carbodiimide resin in the resin composition according to the second embodiment is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, particularly preferably 1% by mass or more, and preferably 10% by mass or less, more preferably 8% by mass or less, particularly preferably 5% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the carbodiimide resin is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric loss tangent at high temperatures, and the insulating reliability can be particularly improved, and furthermore, the relative dielectric constant and the dielectric loss tangent can usually be reduced.

[0175] In a particularly desirable embodiment, the amount of the carbodiimide resin in the resin composition according to the second embodiment is preferably 0.1% by mass or more, more preferably 1% by mass or more, particularly preferably 2% by mass or more, and preferably 20% by mass or less, more preferably 15% by mass or less, particularly preferably 10% by mass or less, based on 100% by mass of the resin components of the resin composition. When the amount of the carbodiimide resin is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric loss tangent at high temperatures, and the insulating reliability can be particularly improved, and furthermore, the relative dielectric constant and the dielectric loss tangent can usually be reduced.

[0176] The (B) curable resin according to the second embodiment may contain a curing agent other than those described above. The curing agent according to the second embodiment may be the same as the curing agent according to the first embodiment. The ratio of the number of active groups of a curing agent such as a phenol resin, an active ester resin, a cyanate resin, a carbodiimide resin, an acid anhydride resin, an amine resin, a benzoxazine resin, or a thiol resin to the number of epoxy groups of the epoxy resin may be the same as that of the first embodiment. That is, in the resin composition according to the second embodiment, the range of the number of active groups of the curing agent when the number of epoxy groups of the epoxy resin is set to 1 may be the same as that described in the first embodiment.

[0177] The range of the amount of the curing agent contained in the resin composition according to the second embodiment may be the same as or different from the range of the amount of the curing agent contained in the resin composition according to the first embodiment.

[0178] In a particularly desirable embodiment, the amount of the curing agent in the resin composition according to the second embodiment is preferably 1% by mass or more, more preferably 5% by mass or more, particularly preferably 10% by mass or more, and preferably 50% by mass or less, more preferably 40% by mass or less, particularly preferably 30% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the curing agent is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric loss tangent at high temperatures, and the insulation reliability can be particularly improved, and furthermore, the relative dielectric constant and the dielectric loss tangent can usually be reduced.

[0179] In a particularly desirable embodiment, the amount of the curing agent in the resin composition according to the second embodiment is preferably 10% by mass or more, more preferably 30% by mass or more, particularly preferably 50% by mass or more, and preferably 90% by mass or less, more preferably 80% by mass or less, particularly preferably 70% by mass or less, based on 100% by mass of the resin components of the resin composition. When the amount of the curing agent is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric loss tangent at high temperatures, and the insulation reliability can be particularly improved, and furthermore, the relative dielectric constant and the dielectric loss tangent can usually be reduced.

[0180] Furthermore, the (B) curable resin according to the second embodiment may contain a radical polymerizable resin. The radical polymerizable resin according to the second embodiment may be the same as the radical polymerizable resin according to the first embodiment. The range of the amount of the radical polymerizable resin contained in the resin composition according to the second embodiment may be the same as or different from the range of the amount of the radical polymerizable resin contained in the resin composition according to the first embodiment.

[0181] In a particularly desirable embodiment, the amount of the radical polymerizable resin in the resin composition according to the second embodiment is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, particularly preferably 0.3% by mass or more, and preferably 10% by mass or less, more preferably 5% by mass or less, particularly preferably 1% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the radical polymerizable resin is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric loss tangent at high temperatures, and the insulating reliability can be particularly improved, and furthermore, the relative dielectric constant and dielectric loss tangent can usually be reduced.

[0182] In a particularly desirable embodiment, the amount of the radical polymerizable resin in the resin composition according to the second embodiment is preferably 0.1% by mass or more, more preferably 0.5% by mass or more, particularly preferably 1% by mass or more, and preferably 20% by mass or less, more preferably 10% by mass or less, particularly preferably 5% by mass or less, based on 100% by mass of the resin components of the resin composition. When the amount of the radical polymerizable resin is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric loss tangent at high temperatures, and the insulating reliability can be particularly improved, and furthermore, the relative dielectric constant and dielectric loss tangent can usually be reduced.

[0183] Among the above, the (B) curable resin according to the second embodiment preferably contains one or more selected from the group consisting of epoxy resin, phenol resin, active ester resin, cyanate resin, (meth)acrylic resin, styryl resin, propenyl resin, and maleimide resin, as in the (B) curable resin according to the first embodiment. In this case, the range of the total amount of the resins selected from the above group may be the same as the range described in the first embodiment. In a particularly desirable aspect, the total amount of the resins selected from the above group is preferably 50% by mass or more, more preferably 70% by mass or more, particularly preferably 90% by mass or more, and preferably 100% by mass or less, more preferably 98% by mass or less, particularly preferably 96% by mass or less, based on 100% by mass of the (B) curable resin. When the (B) curable resin contains such a preferable resin, the crack resistance of the insulating layer, the temperature stability of the dielectric loss tangent at high temperatures, and the insulation reliability can be particularly improved, and moreover, the relative dielectric constant and the dielectric loss tangent can be usually reduced.

[0184] The range of the amount of the (B) curable resin contained in the resin composition according to the second embodiment may be the same as or different from the range of the amount of the (B) curable resin contained in the resin composition according to the first embodiment.

[0185] In a particularly desirable embodiment, the amount of the (B) curable resin in the resin composition according to the second embodiment is preferably 5% by mass or more, more preferably 10% by mass or more, particularly preferably 20% by mass or more, and preferably 60% by mass or less, more preferably 50% by mass or less, particularly preferably 40% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the (B) curable resin is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric tangent at high temperatures, and the insulation reliability can be particularly improved, and furthermore, the relative dielectric constant and the dielectric tangent can usually be reduced.

[0186] In a particularly desirable embodiment, the amount of the (B) curable resin in the resin composition according to the second embodiment is preferably 50% by mass or more, more preferably 60% by mass or more, particularly preferably 70% by mass or more, and preferably 98% by mass or less, more preferably 96% by mass or less, particularly preferably 94% by mass or less, based on 100% by mass of the resin components of the resin composition. When the amount of the (B) curable resin is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric tangent at high temperatures, and the insulation reliability can be particularly improved, and furthermore, the relative dielectric constant and dielectric tangent can usually be reduced.

[0187] <(C) Inorganic filler according to the second embodiment> The resin composition according to the second embodiment of the present invention may further contain an inorganic filler (C) as an optional component. The inorganic filler (C) as the component (C) does not include those corresponding to the above-mentioned components (A) to (B). The inorganic filler (C) is usually contained in the resin composition in the form of particles. The inorganic filler (C) may be used alone or in combination of two or more types. The inorganic filler (C) according to the second embodiment may be the same as the inorganic filler (C) described in the first embodiment. Therefore, the range of the inorganic filler (C) according to the second embodiment may be the same as the range of the inorganic filler (C) according to the first embodiment.

[0188] The range of the amount of the (C) inorganic filler contained in the resin composition according to the second embodiment may be the same as or different from the range of the amount of the (C) inorganic filler contained in the resin composition according to the first embodiment. In a particularly desirable embodiment, the amount of the (C) inorganic filler in the resin composition according to the second embodiment may be 0% by mass, or more than 0% by mass, preferably 40% by mass or more, more preferably 50% by mass or more, particularly preferably 60% by mass or more, and preferably 94% by mass or less, more preferably 90% by mass or less, particularly preferably 85% by mass or less, based on 100% by mass of the non-volatile components of the resin composition. When the amount of the (C) inorganic filler is within the above range, the crack resistance of the insulating layer, the temperature stability of the dielectric loss tangent at high temperatures, and the insulation reliability can be particularly improved, and moreover, the relative dielectric constant and the dielectric loss tangent can be reduced.

[0189] <(D) Curing Accelerator According to Second Embodiment> The resin composition according to the second embodiment of the present invention may further contain a (D) curing accelerator as an optional component. The (D) curing accelerator as the (D) component does not include those corresponding to the above-mentioned (A) to (C) components. The (D) curing accelerator may be used alone or in combination of two or more types. The (D) curing accelerator according to the second embodiment may be the same as the (D) curing accelerator described in the first embodiment. Therefore, the range of the (D) curing accelerator according to the second embodiment may be the same as the range of the (D) curing accelerator according to the first embodiment.

[0190] The range of the amount of the (D) curing accelerator contained in the resin composition according to the second embodiment may be the same as or different from the range of the amount of the (D) curing accelerator contained in the resin composition according to the first embodiment.

[0191] In a particularly desirable aspect, the amount of the (D) curing accelerator in the resin composition according to the second embodiment may be 0% by mass or more than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.02% by mass or more, and particularly preferably 0.03% by mass or more, and is preferably 1.0% by mass or less, more preferably 0.5% by mass or less, and particularly preferably 0.1% by mass or less, relative to 100% by mass of the non-volatile components of the resin composition.

[0192] In a particularly desirable embodiment, the amount of the (D) curing accelerator in the resin composition according to the second embodiment may be 0 mass % or more than 0 mass %, and is preferably 0.01 mass % or more, more preferably 0.05 mass % or more, and particularly preferably 0.1 mass % or more, and is preferably 2.0 mass % or less, more preferably 1.0 mass % or less, and particularly preferably 0.5 mass % or less, relative to 100 mass % of the resin components of the resin composition.

[0193] <Thermoplastic resin (E) according to the second embodiment> The resin composition according to the second embodiment of the present invention may further contain a thermoplastic resin (E) as an optional component. The thermoplastic resin (E) as the component (E) does not include those corresponding to the above-mentioned components (A) to (D). The thermoplastic resin (E) may be used alone or in combination of two or more types. The thermoplastic resin (E) according to the second embodiment may be the same as the thermoplastic resin (E) described in the first embodiment. Therefore, the range of the thermoplastic resin (E) according to the second embodiment may be the same as the range of the thermoplastic resin (E) according to the first embodiment.

[0194] The range of the amount of the (E) thermoplastic resin contained in the resin composition according to the second embodiment may be the same as or different from the range of the amount of the (E) thermoplastic resin contained in the resin composition according to the first embodiment.

[0195] In a particularly desirable aspect, the amount of the (E) thermoplastic resin in the resin composition according to the second embodiment may be 0% by mass or more than 0% by mass, and is preferably 0.01% by mass or more, more preferably 0.1% by mass or more, and particularly preferably 0.5% by mass or more, and is preferably 10% by mass or less, more preferably 5% by mass or less, and particularly preferably 2% by mass or less, relative to 100% by mass of the non-volatile components of the resin composition.

[0196] In a particularly desirable aspect, the amount of the (E) thermoplastic resin in the resin composition according to the second embodiment may be 0% by mass or more than 0% by mass, and is preferably 0.1% by mass or more, more preferably 1% by mass or more, and particularly preferably 2% by mass or more, and is preferably 30% by mass or less, more preferably 20% by mass or less, and particularly preferably 10% by mass or less, relative to 100% by mass of the resin components of the resin composition.

[0197] <Optional Additive (F) According to the Second Embodiment> The resin composition according to the first embodiment of the present invention may further contain an optional additive (F) as an optional non-volatile component. The optional additive (F) as the component (F) does not include those corresponding to the above-mentioned components (A) to (E). The optional additive (F) may be used alone or in combination of two or more. The optional additive (F) according to the second embodiment may be the same as the optional additive (F) described in the first embodiment. Therefore, the range of the optional additive (F) according to the second embodiment may be the same as the range of the optional additive (F) according to the first embodiment.

[0198] <Solvent (G) according to the first embodiment> The resin composition according to the first embodiment of the present invention may further contain a (G) solvent as an optional volatile component in addition to the non-volatile components such as the above-mentioned (A) to (F) components. The (G) solvent may be used alone or in combination of two or more types. The (G) solvent according to the second embodiment may be the same as the (G) solvent described in the first embodiment. Therefore, the range of the (G) solvent according to the second embodiment may be the same as the range of the (G) solvent according to the first embodiment.

[0199] The range of the amount of the (G) solvent contained in the resin composition according to the second embodiment may be the same as or different from the range of the amount of the (G) solvent contained in the resin composition according to the first embodiment.

[0200] <Method of producing resin composition according to second embodiment> The resin composition according to the second embodiment of the present invention can be produced, for example, in the same manner as the resin composition according to the first embodiment, by mixing components that can be contained in the resin composition.

[0201] <Characteristics of the resin composition according to the second embodiment> A cured product is obtained by curing the resin composition according to the second embodiment of the present invention. During the curing, heat is usually applied to the resin composition. Thus, among the components contained in the resin composition, volatile components such as (G) solvent can usually be volatilized by heat during curing, but non-volatile components such as components (A) to (F) do not volatilize by heat during curing. Thus, the cured product of the resin composition can contain the non-volatile components of the resin composition or their reaction products.

[0202] The cured product of the resin composition according to the second embodiment of the present invention has excellent temperature stability of the dielectric tangent at high temperatures. Therefore, the increase in the dielectric tangent of the cured product in a high-temperature environment can be suppressed. Therefore, the increase rate of the dielectric tangent Df (100°C) of the cured product at 100°C relative to the dielectric tangent Df (25°C) of the cured product at 25°C can be reduced. The range of the increase rate is specifically usually 0% or more, usually less than 20%, preferably 19% or less, and more preferably 18% or less. When an insulating layer is formed from a cured product having a low increase rate of the dielectric tangent at high temperatures, an insulating layer having excellent temperature stability of the dielectric tangent at high temperatures can be obtained.

[0203] The rate of increase in the dielectric tangent of the cured product can be measured by the following formula (X). Rate of rise = {Df(100℃)-Df(25℃)} / Df(25℃) (X) (In formula (X), Df(25°C) represents the dielectric tangent at 25°C of a cured product obtained by heat-treating a resin composition at 200°C for 90 minutes, and Df(100°C) represents the dielectric tangent at 100°C of a cured product obtained by heat-treating a resin composition at 200°C for 90 minutes.) The dielectric loss tangent of the cured product can be measured by the method described in <Test Example II-1: Measurement of relative dielectric constant (Dk) and dielectric loss tangent (Df)> in the Examples described below.

[0204] The cured product of the resin composition according to the second embodiment of the present invention has excellent crack resistance. Therefore, when an insulating layer is formed from this cured product, an insulating layer having excellent crack resistance can be obtained. For example, when crack resistance is evaluated by the method described in <Test Example I-2: Evaluation of Crack Resistance> in the examples described later, the yield can be preferably 40% or more, more preferably 60% or more, and particularly preferably 80% or more. Usually, the higher the yield value, the more excellent the crack resistance.

[0205] The cured product of the resin composition according to the second embodiment of the present invention has excellent insulation reliability. Therefore, when an insulating layer is formed from this cured product, an insulating layer with excellent insulation reliability can be obtained. For example, when the insulation reliability is evaluated by the method described in <Test Example II-3: Evaluation of Insulation Reliability> in the examples described later, both the initial resistance value and the resistance value after HAST were 1.0×10 6 The number of samples having a resistance of Ω or more can be preferably 5 or more, more preferably 6 or more, and particularly preferably 7.

[0206] The cured product of the resin composition according to the second embodiment of the present invention can usually have a low dielectric loss tangent. Therefore, when an insulating layer is formed with this cured product, an insulating layer with a low dielectric loss tangent can be obtained. The dielectric loss tangent of the cured product of the resin composition at 25°C is preferably 0.040 or less, more preferably 0.035 or less, and particularly preferably 0.030 or less. There is no particular limit to the lower limit, and it can be, for example, 0.0001 or more. In addition, the dielectric loss tangent of the cured product of the resin composition at 100°C is preferably 0.050 or less, more preferably 0.040 or less, and particularly preferably 0.035 or less. There is no particular limit to the lower limit, and it can be, for example, 0.0001 or more. The dielectric loss tangent of the cured product can be measured by the method described in <Test Example II-1: Measurement of relative dielectric constant (Dk) and dielectric loss tangent (Df)> in the examples described later.

[0207] The cured product of the resin composition according to the second embodiment of the present invention can usually have a low relative dielectric constant. Therefore, when an insulating layer is formed with this cured product, an insulating layer with a low relative dielectric constant can be obtained. The relative dielectric constant of the cured product of the resin composition at 25°C is preferably 4.0 or less, more preferably 3.8 or less, and particularly preferably 3.5 or less. There is no particular restriction on the lower limit, and it can be, for example, 0.1 or more. The dielectric loss tangent of the cured product can be measured by the method described in <Test Example II-1: Measurement of relative dielectric constant (Dk) and dielectric loss tangent (Df)> in the examples described later.

[0208] <Uses of the resin compositions according to the first and second embodiments> In the following description, unless otherwise specified, the term "resin composition" refers to both the resin composition according to the first embodiment and the resin composition according to the second embodiment. The resin composition can be used as a resin composition for insulating purposes, and can be particularly preferably used as a resin composition for forming an insulating layer (resin composition for forming an insulating layer). For example, the resin composition according to this embodiment can be preferably used as a resin composition for forming an insulating layer of a semiconductor chip package (resin composition for insulating layer of a semiconductor chip package) and a resin composition for forming an insulating layer of a circuit board (including a printed wiring board) (resin composition for insulating layer of a circuit board). In particular, the resin composition is suitable for forming an interlayer insulating layer provided between conductor layers.

[0209] Examples of semiconductor chip packages include FC-CSP, MIS-BGA package, ETS-BGA package, Fan-out type WLP (Wafer Level Package), Fan-in type WLP, Fan-out type PLP (Panel Level Package), and Fan-in type PLP.

[0210] The resin composition may also be used as an underfill material, for example, as a material for MUF (Molding Under Filling) that is used after a semiconductor chip is connected to a substrate.

[0211] Furthermore, the resin composition can be used in a wide range of applications in which resin compositions are used, such as sheet-like laminate materials such as resin sheets and prepregs, solder resists, die bonding materials, semiconductor encapsulating materials, hole filling resins, and component embedding resins.

[0212] <Sheet-type laminated material> The resin composition may be used by coating in the form of a varnish, but from an industrial perspective, it is preferable to use the resin composition in the form of a sheet-like laminate material containing the resin composition.

[0213] As the sheet-like laminate material, the following resin sheets and prepregs are preferred.

[0214] In one embodiment, the resin sheet includes a support and a resin composition layer provided on the support. The resin composition layer is formed of the above-mentioned resin composition. Thus, the resin composition layer usually contains a resin composition, and preferably contains only the resin composition.

[0215] The thickness of the resin composition layer is preferably 50 μm or less, more preferably 40 μm or less, from the viewpoint of thinning and of being able to provide a cured product having excellent insulation even if it is thin, by using the resin composition. The lower limit of the thickness of the resin composition layer is not particularly limited, but may be 5 μm or more, 10 μm or more, etc.

[0216] Examples of the support include films made of plastic materials, metal foils, and release papers, with films made of plastic materials and metal foils being preferred.

[0217] When a film made of a plastic material is used as the support, examples of the plastic material include polyesters such as polyethylene terephthalate (hereinafter sometimes abbreviated as "PET") and polyethylene naphthalate (hereinafter sometimes abbreviated as "PEN"), polycarbonate (hereinafter sometimes abbreviated as "PC"), acrylics such as polymethyl methacrylate (PMMA), cyclic polyolefins, triacetyl cellulose (TAC), polyether sulfide (PES), polyether ketone, polyimide, etc. Among these, polyethylene terephthalate and polyethylene naphthalate are preferred, and inexpensive polyethylene terephthalate is particularly preferred.

[0218] When a metal foil is used as the support, examples of the metal foil include copper foil, aluminum foil, etc., and copper foil is preferred. As the copper foil, a foil made of a single metal, copper, or an alloy of copper and another metal (e.g., tin, chromium, silver, magnesium, nickel, zirconium, silicon, titanium, etc.) may be used.

[0219] The surface of the support to be bonded to the resin composition layer may be subjected to a matte treatment, a corona treatment, or an antistatic treatment.

[0220] As the support, a support with a release layer having a release layer on the surface to be bonded to the resin composition layer may be used. The release agent used in the release layer of the support with a release layer may be, for example, one or more release agents selected from the group consisting of alkyd resins, polyolefin resins, urethane resins, and silicone resins. The support with a release layer may be a commercially available product, for example, "SK-1", "AL-5", and "AL-7" manufactured by Lintec Corporation, "Lumirror T60" manufactured by Toray Industries, Inc., "Purex" manufactured by Teijin Limited, and "Unipeel" manufactured by Unitika Limited, which are PET films having a release layer mainly composed of an alkyd resin-based release agent.

[0221] The thickness of the support is not particularly limited, but is preferably in the range of 5 μm to 75 μm, and more preferably in the range of 10 μm to 60 μm. When a support with a release layer is used, it is preferable that the total thickness of the support with a release layer is in the above range.

[0222] In one embodiment, the resin sheet may further include an optional layer as necessary. For example, such an optional layer may be a protective film equivalent to the support provided on the surface of the resin composition layer that is not bonded to the support (i.e., the surface opposite to the support). The thickness of the protective film is not particularly limited, but is, for example, 1 μm to 40 μm. By laminating the protective film, it is possible to suppress adhesion of dirt and scratches on the surface of the resin composition layer.

[0223] The resin sheet can be produced, for example, by preparing a liquid (varnish-like) resin composition as is or by dissolving the resin composition in a solvent to prepare a liquid (varnish-like) resin composition, applying this onto a support using a die coater or the like, and then drying to form a resin composition layer.

[0224] The solvent may be the same as the solvent explained as a component of the resin composition. The solvent may be used alone or in combination of two or more.

[0225] Drying may be performed by heating, blowing hot air, or the like. Drying conditions are not particularly limited, but drying is performed so that the content of the solvent in the resin composition layer is usually 10% by mass or less, preferably 5% by mass or less. Although it varies depending on the boiling point of the solvent in the resin composition, for example, when a resin composition containing 30% by mass to 60% by mass of a solvent is used, the resin composition layer can be formed by drying at 50°C to 150°C for 3 minutes to 10 minutes.

[0226] The resin sheet can be stored in a rolled state. When the resin sheet has a protective film, it is usually possible to use the resin sheet by peeling off the protective film.

[0227] In one embodiment, the prepreg is formed by impregnating a sheet-like fiber substrate with the resin composition according to this embodiment.

[0228] The sheet-like fiber substrate used for the prepreg may be, for example, a commonly used substrate for prepreg, such as glass cloth, aramid nonwoven fabric, or liquid crystal polymer nonwoven fabric. From the viewpoint of thinning, the thickness of the sheet-like fiber substrate is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 30 μm or less, and particularly preferably 20 μm or less. The lower limit of the thickness of the sheet-like fiber substrate is not particularly limited, and is usually 10 μm or more.

[0229] The prepreg can be produced by a method such as a hot melt method or a solvent method.

[0230] The thickness of the prepreg can be in the same range as that of the resin composition layer in the resin sheet described above.

[0231] The sheet-like laminate material can be suitably used, for example, to form an insulating layer in the manufacture of a semiconductor chip package (resin sheet for insulating a semiconductor chip package). Examples of applicable semiconductor chip packages include fan-out type WLP, fan-in type WLP, fan-out type PLP, and fan-in type PLP. The sheet-like laminate material can also be used, for example, to form an insulating layer of a circuit board (resin sheet for insulating layer of a circuit board). Furthermore, the sheet-like laminate material may be used as a material for a MUF used after connecting a semiconductor chip to a board. In particular, the sheet-like laminate material is suitable for forming an interlayer insulating layer.

[0232] <Circuit board> A circuit board according to one embodiment of the present invention includes a cured product of a resin composition. Usually, the circuit board includes an insulating layer formed of the cured product of the resin composition. The insulating layer includes the cured product of the above-mentioned resin composition, and preferably includes only the cured product of the above-mentioned resin composition. This circuit board can be manufactured, for example, by a manufacturing method including the following steps (I) and (II). (I) A step of forming a resin composition layer on an inner layer substrate. (II) A step of curing the resin composition layer to form an insulating layer.

[0233] The "inner layer substrate" used in step (I) is a member that serves as the base material of a circuit board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, and a thermosetting polyphenylene ether substrate. The substrate may have a conductor layer on one or both sides, and the conductor layer may be patterned. An inner layer substrate having a conductor layer (circuit) formed on one or both sides of the substrate may be called an "inner layer circuit substrate". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be further formed during the manufacture of a circuit substrate is also included in the above-mentioned "inner layer substrate". When the circuit substrate is a circuit board with built-in components, an inner layer substrate with built-in components may be used.

[0234] When the conductor layer of the inner layer substrate is patterned, the minimum line / space ratio of the conductor layer is preferably small in order to utilize the advantage of excellent crack resistance. "Line" refers to the circuit width of the conductor layer, and "space" refers to the distance between the circuits. The range of the minimum line / space ratio is preferably 20 / 20 μm or less (i.e., pitch is 40 μm or less), more preferably 15 / 15 μm or less, and even more preferably 10 / 10 μm or less. The lower limit may be, for example, 0.5 / 0.5 μm or more. The pitch may be uniform or non-uniform throughout the conductor layer. The minimum pitch of the conductor layer may be, for example, 40 μm or less, 36 μm or less, or 30 μm or less.

[0235] The resin composition layer can be formed on the inner layer substrate by, for example, laminating the inner layer substrate and the resin sheet. The inner layer substrate and the resin sheet can be laminated by, for example, thermocompression bonding the resin sheet to the inner layer substrate from the support side. Examples of the member for thermocompression bonding the resin sheet to the inner layer substrate (hereinafter also referred to as the "thermocompression bonding member") include a heated metal plate (such as a SUS plate) or a metal roll (SUS roll). It is preferable to press the thermocompression bonding member through an elastic material such as heat-resistant rubber so that the resin sheet can sufficiently follow the surface irregularities of the inner layer substrate, rather than directly pressing the resin sheet with the thermocompression bonding member.

[0236] The lamination of the inner layer substrate and the resin sheet may be performed by a vacuum lamination method. In the vacuum lamination method, the thermocompression temperature is preferably in the range of 60°C to 160°C, more preferably in the range of 80°C to 140°C, the thermocompression pressure is preferably in the range of 0.098MPa to 1.77MPa, more preferably in the range of 0.29MPa to 1.47MPa, and the thermocompression time is preferably in the range of 20 seconds to 400 seconds, more preferably in the range of 30 seconds to 300 seconds. The lamination is preferably performed under reduced pressure conditions of 26.7hPa or less.

[0237] The lamination can be performed by a commercially available vacuum laminator, such as a vacuum pressure laminator manufactured by Meiki Seisakusho Co., Ltd., a vacuum applicator manufactured by Nikko Materials Co., Ltd., or a batch type vacuum pressure laminator.

[0238] After lamination, the laminated resin sheet may be smoothed under normal pressure (atmospheric pressure), for example, by pressing a thermocompression member from the support side. The pressing conditions for the smoothing treatment may be the same as the thermocompression conditions for the lamination. The smoothing treatment may be performed using a commercially available laminator. The lamination and smoothing treatment may be performed consecutively using the commercially available vacuum laminator.

[0239] The support may be removed between step (I) and step (II) or after step (II).

[0240] In step (II), the resin composition layer is cured to form an insulating layer made of a cured product of the resin composition. The resin composition layer can be cured by a method suitable for the resin composition, such as thermal curing or photocuring. Specific curing conditions for the resin composition layer may be the conditions usually adopted when forming an insulating layer for a circuit board.

[0241] When a thermosetting resin composition is used, the curing of the resin composition may proceed as heat curing. Therefore, in this case, step (II) may include heat curing the resin composition layer. The heat curing conditions of the resin composition layer may vary depending on the type of resin composition. For example, the curing temperature is preferably 120°C to 240°C, more preferably 150°C to 220°C, and even more preferably 170°C to 210°C. The curing time may be preferably 5 minutes to 120 minutes, more preferably 10 minutes to 100 minutes, and even more preferably 15 minutes to 100 minutes.

[0242] In addition, when the resin composition layer is thermally cured, the method for producing a circuit board preferably includes preheating the resin composition layer at a temperature lower than the curing temperature before the thermal curing. For example, prior to thermal curing of the resin composition layer, the resin composition layer may be preheated at a temperature of usually 50° C. to 150° C., preferably 60° C. to 140° C., more preferably 70° C. to 130° C. for usually 5 minutes or more, preferably 5 minutes to 150 minutes, more preferably 15 minutes to 120 minutes, and even more preferably 15 minutes to 100 minutes.

[0243] On the other hand, when a photocurable resin composition is used, the curing of the resin composition may proceed as photocuring. In this case, therefore, step (II) may include photocuring the resin composition layer. The photocuring conditions of the resin composition may vary depending on the type of resin composition. For example, the resin composition layer in the irradiated area may be photocured by exposure treatment in which the resin composition layer is irradiated with actinic rays. Examples of actinic rays include ultraviolet rays, visible rays, electron beams, X-rays, etc., and ultraviolet rays are particularly preferred. The irradiation dose of ultraviolet rays is, for example, 10 mJ / cm. 2 ~1000mJ / cm 2 When a resin sheet having a support is used, exposure may be performed through the support, or after the support is peeled off.

[0244] In the exposure treatment, the resin composition layer may be irradiated with active light through a mask having a pattern formed thereon. Exposure methods using a mask include a contact exposure method in which exposure is performed by bringing a mask into contact with a workpiece, and a non-contact exposure method in which exposure is performed using parallel light without contact, and either method may be used.

[0245] Step (II) may include carrying out a development treatment after the exposure treatment. According to the development treatment, the part not photocured (unexposed part) can be removed to form a pattern in the cured body layer. The development is usually carried out by wet development. In the wet development, a developer that is safe, stable, and easy to operate, such as an alkaline aqueous solution, a water-based developer, or an organic solvent, is used. Among them, a development step using an alkaline aqueous solution is preferred. As the development method, for example, a method such as spraying, swing immersion, brushing, or scraping can be adopted.

[0246] Furthermore, in the case where the resin composition layer is photocured, a post-baking treatment may be carried out as necessary after photocuring and development. Examples of the post-baking treatment include ultraviolet irradiation treatment using a high-pressure mercury lamp and heating treatment using a clean oven. The ultraviolet irradiation treatment is carried out at a dose of, for example, 0.05 J / cm. 2 ~10J / cm 2 The heat treatment can be carried out, for example, at a temperature of preferably 150° C. to 250° C. for 20 minutes to 180 minutes, and more preferably at a temperature of 160° C. to 230° C. for 30 minutes to 120 minutes.

[0247] In producing a circuit board, the steps of (III) drilling holes in the insulating layer, (IV) roughening the insulating layer, and (V) forming a conductor layer may be further carried out. These steps (III) to (V) may be carried out according to various methods known to those skilled in the art that are used in producing circuit boards. When the support is removed after step (II), the removal of the support may be carried out between step (II) and step (III), between step (III) and step (IV), or between step (IV) and step (V). If necessary, the formation of the insulating layer and the conductor layer in steps (I) to (V) may be repeated to form a circuit board having a multilayer structure such as a multilayer printed wiring board.

[0248] In another embodiment, the circuit board can be manufactured using the above-mentioned prepreg. The manufacturing method can be basically the same as when a resin sheet is used.

[0249] Step (III) is a step of drilling holes in the insulating layer, which allows holes such as via holes and through holes to be formed in the insulating layer. Step (III) may be performed using, for example, a drill, a laser, plasma, etc., depending on the composition of the resin composition used to form the insulating layer. The size and shape of the hole may be appropriately determined depending on the design of the circuit board.

[0250] Step (IV) is a step of roughening the insulating layer. Usually, in this step (IV), smears are also removed. Therefore, the roughening treatment is sometimes called "desmear treatment". The procedure and conditions of the roughening treatment are not particularly limited, and known procedures and conditions that are usually used when forming an insulating layer of a circuit board can be adopted. For example, the insulating layer can be roughened by performing a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order.

[0251] Examples of the swelling liquid used in the roughening treatment include an alkaline solution and a surfactant solution, and an alkaline solution is preferred. As the alkaline solution, a sodium hydroxide solution and a potassium hydroxide solution are more preferred. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment using a swelling liquid can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 to 20 minutes. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferred to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 to 15 minutes.

[0252] An example of an oxidizing agent used in the roughening treatment is an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 minutes to 30 minutes. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan.

[0253] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and a commercially available product is, for example, "Reduction Solution Securigant P" manufactured by Atotech Japan. Treatment with a neutralizing solution can be performed by immersing the surface that has been roughened with an oxidizing agent in a neutralizing solution at 30°C to 80°C for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the object that has been roughened with an oxidizing agent is immersed in a neutralizing solution at 40°C to 70°C for 5 to 20 minutes is preferred.

[0254] Step (V) is a step of forming a conductor layer, and the conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among these, from the viewpoints of versatility in forming the conductor layer, cost, ease of patterning, and the like, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred.

[0255] The conductor layer may be a single-layer structure, or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. When the conductor layer has a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.

[0256] The thickness of the conductor layer depends on the desired design of the circuit board, but is generally 3 μm to 35 μm, and preferably 5 μm to 30 μm.

[0257] In one embodiment, the conductor layer may be formed by plating. For example, a conductor layer having a desired wiring pattern can be formed by plating the surface of the insulating layer by a conventionally known technique such as a semi-additive method or a full-additive method. From the viewpoint of ease of production, the semi-additive method is preferred. Below, an example of forming the conductor layer by the semi-additive method is shown.

[0258] First, a plating seed layer is formed on the surface of an insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer having a desired wiring pattern.

[0259] In another embodiment, the conductor layer may be formed using a metal foil. When the conductor layer is formed using a metal foil, it is preferable to carry out step (V) between steps (I) and (II). For example, after step (I), the support is removed, and a metal foil is laminated on the exposed surface of the resin composition layer. The lamination of the resin composition layer and the metal foil may be carried out by a vacuum lamination method. The lamination conditions may be the same as those described for step (I). Next, step (II) is carried out to form an insulating layer. Thereafter, a conductor layer having a desired wiring pattern can be formed by a conventionally known technique such as a subtractive method or a modified semi-additive method, using the metal foil on the insulating layer.

[0260] The metal foil can be produced by a known method such as an electrolytic method, a rolling method, etc. Commercially available metal foils include, for example, HLP foil and JXUT-III foil manufactured by JX Nippon Mining & Metals Corporation, and 3EC-III foil and TP-III foil manufactured by Mitsui Mining & Smelting Co., Ltd.

[0261] <Semiconductor chip package> A semiconductor chip package according to an embodiment of the present invention includes a cured resin composition. Typically, the semiconductor chip package includes an insulating layer formed of the cured resin composition. The insulating layer includes the cured resin composition described above, and preferably includes only the cured resin composition described above. Examples of this semiconductor chip package include the following.

[0262] The semiconductor chip package according to the first example includes the above-mentioned circuit board and a semiconductor chip mounted on the circuit board. This semiconductor chip package can be manufactured by bonding the semiconductor chip to the circuit board.

[0263] The bonding conditions between the circuit board and the semiconductor chip may be any conditions that allow conductive connection between the terminal electrodes of the semiconductor chip and the circuit wiring of the circuit board. For example, the conditions used in flip-chip mounting of the semiconductor chip may be used. Also, for example, the semiconductor chip and the circuit board may be bonded via an insulating adhesive.

[0264] An example of a bonding method is a method of bonding a semiconductor chip to a circuit board. The bonding conditions are that the bonding temperature is usually in the range of 120°C to 240°C (preferably in the range of 130°C to 200°C, more preferably in the range of 140°C to 180°C), and the bonding time is usually in the range of 1 second to 60 seconds (preferably in the range of 5 seconds to 30 seconds).

[0265] Another example of the bonding method is a method of bonding a semiconductor chip to a circuit board by reflow. The reflow conditions may be in the range of 120°C to 300°C.

[0266] After the semiconductor chip is bonded to the circuit board, the semiconductor chip may be filled with a molded underfill material, which may be the resin composition described above.

[0267] The semiconductor chip package according to the second example includes a semiconductor chip and an insulating layer formed of a cured product of a resin composition. Examples of the semiconductor chip package according to the second example include a fan-out type WLP and a fan-out type PLP.

[0268] Fig. 1 is a cross-sectional view showing a fan-out type WLP as an example of a semiconductor chip package according to an embodiment of the present invention. A semiconductor chip package 100 as a fan-out type WLP includes, for example, a semiconductor chip 110, a sealing layer 120 formed to cover the periphery of the semiconductor chip 110, a rewiring formation layer 130 as an insulating layer provided on the surface of the semiconductor chip 110 opposite to the sealing layer 120, a rewiring layer 140 as a conductor layer, a solder resist layer 150, and bumps 160, as shown in Fig. 1.

[0269] The method for manufacturing such a semiconductor chip package includes: (A) a step of laminating a temporary fixing film on a substrate; (B) a step of temporarily fixing a semiconductor chip on a temporary fixing film; (C) forming an encapsulation layer on the semiconductor chip; (D) peeling the substrate and the temporary fixing film from the semiconductor chip; (E) a step of forming a rewiring formation layer on the surface from which the substrate and the temporary fixing film of the semiconductor chip have been peeled off; (F) forming a rewiring layer as a conductor layer on the rewiring formation layer; and (G) forming a solder resist layer on the rewiring layer; The method for manufacturing the semiconductor chip package further comprises: (H) A process of dicing and separating multiple semiconductor chip packages into individual semiconductor chip packages. may also include

[0270] (Process (A)) Step (A) is a step of laminating a temporary fixing film on a substrate. The lamination conditions for the substrate and the temporary fixing film can be the same as the lamination conditions for the substrate and the resin sheet in the method for producing a circuit board.

[0271] Examples of the substrate include silicon wafers; glass wafers; glass substrates; metal substrates such as copper, titanium, stainless steel, and cold-rolled steel (SPCC); substrates such as FR-4 substrates in which glass fibers are impregnated with epoxy resin or the like and then heat-cured; and substrates made of bismaleimide triazine resins such as BT resin.

[0272] The temporary fixing film may be made of any material that can be peeled off from the semiconductor chip and can temporarily fix the semiconductor chip. Commercially available products include "Riva Alpha" manufactured by Nitto Denko Corporation.

[0273] (Process (B)) Step (B) is a step of temporarily fixing the semiconductor chip on the temporary fixing film. The temporary fixing of the semiconductor chip can be performed using, for example, a device such as a flip chip bonder or a die bonder. The layout and number of the semiconductor chips can be appropriately set depending on the shape and size of the temporary fixing film, the number of semiconductor chip packages to be produced, etc. For example, the semiconductor chips may be temporarily fixed by arranging them in a matrix shape of multiple rows and multiple columns.

[0274] (Process (C)) Step (C) is a step of forming an encapsulating layer on the semiconductor chip. The encapsulating layer can be formed, for example, from a photosensitive resin composition or a thermosetting resin composition. This encapsulating layer may be formed from a cured product of the resin composition according to the above-mentioned embodiment. The encapsulating layer can usually be formed by a method including a step of forming a resin composition layer on the semiconductor chip and a step of curing this resin composition layer to form the encapsulating layer.

[0275] (Process (D)) Step (D) is a step of peeling off the substrate and the temporary fixing film from the semiconductor chip. It is desirable to adopt an appropriate peeling method according to the material of the temporary fixing film. For example, the peeling method may be a method of heating, foaming or expanding the temporary fixing film to peel it off. In addition, for example, the peeling method may be a method of irradiating the temporary fixing film with ultraviolet light through the substrate to reduce the adhesive strength of the temporary fixing film to peel it off.

[0276] When the base material and the temporary fixing film are peeled off from the semiconductor chip as described above, the surface of the encapsulating layer is exposed. The manufacturing method of the semiconductor chip package may include polishing the exposed surface of the encapsulating layer. By polishing, the smoothness of the surface of the encapsulating layer can be improved.

[0277] (Process (E)) Step (E) is a step of forming a rewiring formation layer as an insulating layer on the surface of the semiconductor chip from which the base material and the temporary fixing film are peeled off. Usually, this rewiring formation layer is formed on the semiconductor chip and the sealing layer. The rewiring formation layer can be formed by a cured product of the resin composition according to the above-mentioned embodiment. Usually, the rewiring formation layer can be formed by a method including a step of forming a resin composition layer on the semiconductor chip and a step of curing the resin composition layer to form the rewiring formation layer. The formation of the resin composition layer on the semiconductor chip can be performed by the same method as the method of forming the resin composition layer on the inner layer substrate described in the above-mentioned method for producing a circuit board, except that a semiconductor chip is used instead of the inner layer substrate.

[0278] After forming a resin composition layer on a semiconductor chip, the resin composition layer is cured to obtain a rewiring formation layer as an insulating layer containing a cured product of the resin composition. The curing conditions of the resin composition layer may be the same as the curing conditions of the resin composition layer in the manufacturing method of a circuit board. When the resin composition layer is thermally cured, the resin composition layer may be subjected to a preheating treatment in which the resin composition layer is heated at a temperature lower than the curing temperature before the thermal curing. The treatment conditions of this preheating treatment may be the same as the preheating treatment in the manufacturing method of a circuit board. Usually, after forming the rewiring formation layer, holes are formed in the rewiring formation layer to connect the semiconductor chip and the rewiring layer.

[0279] (Process (F)) Step (F) is a step of forming a rewiring layer as a conductor layer on the rewiring formation layer. The method of forming the rewiring layer on the rewiring formation layer can be the same as the method of forming a conductor layer on an insulating layer in the manufacturing method of a circuit board. Steps (E) and (F) may be repeated to alternately stack (build up) the rewiring layers and the rewiring formation layers.

[0280] (Process (G)) Step (G) is a step of forming a solder resist layer on the rewiring layer. Any material having insulating properties can be used as the material of the solder resist layer. Among them, from the viewpoint of ease of manufacturing the semiconductor chip package, a photosensitive resin composition and a thermosetting resin composition are preferable. The solder resist layer may be formed by a cured product of the resin composition according to the above-mentioned embodiment.

[0281] In step (G), bumping processing may be performed to form bumps, if necessary. The bumping processing may be performed by a method such as solder balls or solder plating. In addition, the formation of via holes in the bumping processing may be performed in the same manner as in step (E).

[0282] (Process (H)) The method for manufacturing a semiconductor chip package may include a step (H) in addition to the steps (A) to (G). The step (H) is a step of dicing a plurality of semiconductor chip packages into individual semiconductor chip packages to separate them. The method for dicing the semiconductor chip packages into individual semiconductor chip packages is not particularly limited.

[0283] <Semiconductor device> The semiconductor device includes the above-mentioned circuit board or semiconductor chip package. Examples of the semiconductor device include various semiconductor devices used in electrical products (e.g., computers, mobile phones, smartphones, tablet devices, wearable devices, digital cameras, medical devices, televisions, etc.) and vehicles (e.g., motorcycles, automobiles, trains, ships, aircraft, etc.). EXAMPLES

[0284] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the following examples. In the following description, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Furthermore, the temperature and pressure conditions were room temperature (25°C) and atmospheric pressure (1 atm), unless otherwise specified. In the following description, "L / S" represents the line / space ratio of the wiring pattern, unless otherwise specified.

[0285] <Synthesis Example 1> In a 1L reaction vessel equipped with a thermometer, a stirrer and a cooling tube, 410g of methanol, 48.0g of sodium hydroxide and 205.0g of biphenol were charged, and 91.8g of allyl chloride was added dropwise at 40°C over 3 hours while paying attention to heat generation. After that, the temperature was raised to the temperature at which methanol refluxes (about 60°C), and an allyl etherification reaction was carried out for 4 hours. Next, after removing salts by washing with water, the temperature was raised to 180°C, and a transfer reaction was carried out for 10 hours. After the transfer reaction, the temperature was lowered to 100°C, 205.0g of butanol was added to dissolve the resin, and 70.5g of potassium hydroxide was added, and a propenylation reaction was carried out at 115°C for 6 hours. Then, the mixture was washed with water and concentrated to obtain a propenyl resin represented by the above formula (b1) (propenyl form of biphenol, hydroxyl equivalent 133g / eq.).

[0286] <Explanation of Example Group I> <Example I-1> 20 parts of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent of about 269 g / eq.) and 10 parts of bisphenol type epoxy resin ("ZX1059" manufactured by Nippon Steel Chemical & Material Co., Ltd., 1:1 mixture of bisphenol A type and bisphenol F type, epoxy equivalent of about 169 g / eq.) were dissolved in 25 parts of solvent naphtha with stirring to obtain a solution. This solution was cooled to room temperature to prepare a dissolved composition of the epoxy resin.

[0287] To this epoxy resin solution, 5 parts of polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industries, average particle size 0.3 μm), 100 parts of an active ester compound ("HPC-8150-62T" manufactured by DIC Corporation, active ester group equivalent of about 220 g / eq., non-volatile content of 62% by mass in toluene solution), and 100 parts of a triazine skeleton-containing phenolic hardener ("LA-3018-50P" manufactured by DIC Corporation, active group equivalent of about 151 g / eq., 2-methoxypropanol solution with non-volatile content of 50%) 10 parts, carbodiimide curing agent (Nisshinbo Chemical Co., Ltd. "V-03", active group equivalent of approximately 216 g / eq., toluene solution with non-volatile content of 50%) 15 parts, spherical silica (Admatechs Co., Ltd. "SO-C2", average particle size 0.5 μm, specific surface area 5.8 m) surface-treated with a silane coupling agent (Shin-Etsu Chemical Co., Ltd. "KBM-573"). 2 A resin composition was prepared by mixing 300 parts of a methyl ketone (MEK) (1:1 solution with a non-volatile content of 30% by mass) and a curing accelerator (4-dimethylaminopyridine (DMAP)) (g), 0.2 parts of a curing accelerator (4-dimethylaminopyridine (DMAP)), and 10 parts of a phenoxy resin (YX7553BH30 manufactured by Mitsubishi Chemical Corporation, a 1:1 solution of MEK and cyclohexanone with a non-volatile content of 30% by mass).

[0288] <Example I-2> The amount of polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industries, Ltd., average particle size 0.3 μm) was increased from 5 parts to 20 parts. Furthermore, instead of 100 parts of an active ester compound ("HPC-8150-62T" manufactured by DIC Corporation, active ester group equivalent of about 220 g / eq., toluene solution with non-volatile content of 62 mass%), 100 parts of an active ester compound ("HPC-8000-65T" manufactured by DIC Corporation, active ester group equivalent of about 223 g / eq., toluene solution with non-volatile content of 65%) was used. A resin composition was prepared in the same manner as in Example I-1, except for the above points.

[0289] <Example I-3> Instead of 5 parts of polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industries, average particle size 0.3 μm), 5 parts of polystyrene / acrylic copolymer fine particles ("SEP-03T3A" manufactured by Negami Chemical Industries, average particle size 0.3 μm) were used. In addition, spherical silica ("SO-C2" manufactured by Admatechs Co., Ltd., average particle size 0.5 μm, specific surface area 5.8 m) surface-treated with a silane coupling agent ("KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd.) was used. 2 The amount of cellulose acetate / g was reduced from 300 parts to 210 parts. Furthermore, 6 parts of hollow aluminosilicate particles ("MG-005" manufactured by Taiheiyo Cement Corporation, hollow inorganic filler, average particle size 1.6 μm, porosity 80% by volume) were further added to the resin composition. A resin composition was prepared in the same manner as in Example I-1, except for the above points.

[0290] <Example I-4> Instead of 5 parts of polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industries, average particle size 0.3 μm), 5 parts of polystyrene fine particles ("XX-6283Z" manufactured by Sekisui Chemical Industries, average particle size 0.3 μm) were used. A resin composition was prepared in the same manner as in Example I-1, except for the above points.

[0291] <Example I-5> Instead of 5 parts of polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industries, average particle size 0.3 μm), 5 parts of polystyrene fine particles to which a carboxy group was added ("XX-6288Z" manufactured by Sekisui Chemical Industries, average particle size 0.3 μm) were used. A resin composition was prepared in the same manner as in Example I-1, except for the above points.

[0292] <Example I-6> Instead of 5 parts of polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industrial Co., Ltd., average particle size 0.3 μm), 5 parts of polystyrene fine particles ("GS-0305" manufactured by Aica Kogyo Co., Ltd., average particle size 3.0 μm) were used. A resin composition was prepared in the same manner as in Example I-1, except for the above.

[0293] <Example I-7> Instead of 5 parts of polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industries, average particle size 0.3 μm), 5 parts of polyethylene fine particles ("SB-25" manufactured by Morimoto Chemical Co., Ltd., average particle size 2.5 μm) were used. Except for the above, a resin composition was prepared in the same manner as in Example I-1.

[0294] <Example I-8> Instead of 20 parts of biphenyl-type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent of about 269 g / eq.) and 10 parts of bisphenol-type epoxy resin ("ZX1059" manufactured by Nippon Steel Chemical & Material Co., Ltd., 1:1 mixture of bisphenol A type and bisphenol F type, epoxy equivalent of about 169 g / eq.), 20 parts of naphthalene-type epoxy resin ("HP-4032-SS" manufactured by DIC Corporation, 1,6-bis(glycidyloxy)naphthalene, epoxy equivalent of about 145 g / eq.) and 10 parts of bixylenol-type epoxy resin ("YX4000H" manufactured by Mitsubishi Chemical Co., Ltd., epoxy equivalent of 190 g / eq.) were used. Furthermore, 3 parts of biphenylaralkylnovolac-type maleimide ("MIR-3000-70MT" manufactured by Nippon Kayaku Co., Ltd., MEK / toluene mixed solution with non-volatile content of 70%) were added to the resin composition. A resin composition was prepared in the same manner as in Example I-1, except for the above.

[0295] <Example I-9> Instead of 3 parts of biphenylaralkylnovolac-type maleimide ("MIR-3000-70MT" manufactured by Nippon Kayaku Co., Ltd., a mixed solution of MEK / toluene with a non-volatile content of 70%), 5 parts of vinylbenzyl-modified polyphenylene ether ("OPE-2St 2200" manufactured by Mitsubishi Gas Chemical Co., Ltd., a toluene solution with a non-volatile content of 65%) was used. A resin composition was prepared in the same manner as in Example I-8, except for the above points.

[0296] <Example I-10> Instead of 5 parts of polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industries, average particle size 0.3 μm), 3 parts of polystyrene / acrylic copolymer fine particles ("SEP-03T3A" manufactured by Negami Chemical Industries, average particle size 0.3 μm) and 2 parts of polystyrene fine particles ("XX-6283Z" manufactured by Sekisui Chemical Industries, average particle size 0.3 μm) were used. In addition, instead of 3 parts of biphenylaralkylnovolac type maleimide ("MIR-3000-70MT" manufactured by Nippon Kayaku Co., Ltd., MEK / toluene mixed solution with non-volatile content of 70%), 3 parts of the propenyl resin obtained in Synthesis Example 1 were used. Except for the above, a resin composition was prepared in the same manner as in Example I-8.

[0297] <Example I-11> Instead of 100 parts of an active ester compound (DIC Corporation's "HPC-8150-62T", active ester group equivalent of about 220 g / eq., toluene solution with non-volatile content of 62% by mass), 10 parts of a triazine skeleton-containing phenolic hardener (DIC Corporation's "LA-3018-50P", active group equivalent of about 151 g / eq., 2-methoxypropanol solution with non-volatile content of 50%) and 15 parts of a carbodiimide hardener (Nisshinbo Chemical Corporation's "V-03", active group equivalent of about 216 g / eq., toluene solution with non-volatile content of 50%), 40 parts of a novolac-type phenolic hardener (DIC Corporation's "TD-2090", active group equivalent of about 105 g / eq., solution with non-volatile content of 60%) was used. In addition, spherical silica (Admatechs' "SO-C2", average particle size 0.5 μm, specific surface area 5.8 m) that was surface-treated with a silane coupling agent (Shin-Etsu Chemical's "KBM-573") was used. 2 The amount of ethyl alcohol (100 parts / g) was reduced from 300 parts to 50 parts. Furthermore, 0.1 parts of an imidazole-based curing accelerator (1-benzyl-2-phenylimidazole, "1B2PZ" manufactured by Shikoku Chemical Industry Co., Ltd.) was used in place of 0.2 parts of the curing accelerator (4-dimethylaminopyridine (DMAP)). A resin composition was prepared in the same manner as in Example I-1, except for the above points.

[0298] <Example I-12> Instead of 100 parts of an active ester compound (DIC Corporation's "HPC-8150-62T", active ester group equivalent of about 220 g / eq., toluene solution with non-volatile content of 62% by mass), 10 parts of a triazine skeleton-containing phenolic hardener (DIC Corporation's "LA-3018-50P", active group equivalent of about 151 g / eq., 2-methoxypropanol solution with non-volatile content of 50%) and 15 parts of a carbodiimide hardener (Nisshinbo Chemical Corporation's "V-03", active group equivalent of about 216 g / eq., toluene solution with non-volatile content of 50%), 15 parts of an active ester compound (DIC Corporation's "HPC-8000-65T", active ester group equivalent of about 223 g / eq., toluene solution with non-volatile content of 65%) and a prepolymer of bisphenol A dicyanate (Lonza Japan's "Primaset 20 parts of MEK solution containing "BA230S75", cyanate equivalent of about 232 g / eq. and non-volatile components of 75% by mass) were used. In addition, spherical silica ("SO-C2" manufactured by Admatechs Co., Ltd., average particle size 0.5 μm, specific surface area 5.8 m) surface-treated with a silane coupling agent ("KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd.) was used. 2 The amount of cellulose acetate (CO2) was reduced from 300 parts to 60 parts. Furthermore, 0.01 parts of cobalt (III) acetylacetonate (Tokyo Chemical Industry Co., Ltd., Co(III)AcAc) was added to the resin composition. A resin composition was prepared in the same manner as in Example I-1, except for the above points.

[0299] <Comparative example I-1> A resin composition was prepared in the same manner as in Example I-1, except that polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industrial Co., Ltd., average particle size 0.3 μm) were not used.

[0300] <Comparative example I-2> Instead of 5 parts of polystyrene fine particles (Negami Chemical Industries, "SEP-03T3", average particle size 0.3 μm), 5 parts of core-shell structure rubber particles (Aica Chemical Industries, "Staphyloid AC3816N", core part is acrylic resin, shell part is polymethacrylate resin, average particle size 0.3 μm) were used. Biphenyl aralkyl novolac type maleimide (Nippon Kayaku Co., Ltd., "MIR-3000-70MT", MEK / toluene mixed solution with non-volatile content of 70%) was not used. A resin composition was prepared in the same manner as in Example I-8 except for the above.

[0301] <Comparative example I-3> Instead of 5 parts of polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industries, average particle size 0.3 μm), 5 parts of polystyrene particles ("G-800T" manufactured by Negami Chemical Industries, average particle size 6.0 μm) were used. In addition, biphenylaralkylnovolac type maleimide ("MIR-3000-70MT" manufactured by Nippon Kayaku Co., Ltd., MEK / toluene mixed solution with non-volatile content of 70%) was not used. A resin composition was prepared in the same manner as in Example I-8 except for the above.

[0302] <Comparative example I-4> A resin composition was prepared in the same manner as in Example I-12, except that polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industrial Co., Ltd., average particle size 0.3 μm) were not used.

[0303] <Production of resin sheets> A polyethylene terephthalate film with a release layer ("AL5" manufactured by Lintec Corporation, thickness 38 μm) was prepared as a support. The resin compositions obtained in the above-mentioned Examples and Comparative Examples were uniformly applied onto the release layer of this support so that the thickness of the resin composition layer after drying was 40 μm. Thereafter, the resin composition was dried at 80°C to 100°C (average 90°C) for 4 minutes to obtain a resin sheet including a support and a resin composition layer.

[0304] <Test Example I-1: Measurement of relative dielectric constant (Dk) and dielectric loss tangent (Df)> The resin sheet was heated at 200°C for 90 minutes to heat-cure the resin composition layer, and then the support was peeled off to obtain a cured film formed of the cured product of the resin composition. The cured film was cut into a piece having a width of 2 mm and a length of 80 mm to obtain a cured product A for evaluation.

[0305] The dielectric constant (Dk) and dielectric loss tangent (Df) of the obtained cured product A for evaluation were measured by the cavity resonance perturbation method at a measurement frequency of 5.8 GHz and a measurement temperature of 23° C. using an “HP8362B” manufactured by Agilent Technologies. Measurements were performed on three test pieces, and the average values ​​were calculated.

[0306] <Test Example I-2: Evaluation of crack resistance> (1) Lamination of resin sheet: An inner layer substrate (Hitachi Chemical's "MCL-E700G", conductor layer thickness 35 μm, total thickness 0.4 mm, residual copper ratio 40%) having circuit conductors (copper) formed as a wiring pattern of L / S = 8 μm / 8 μm on both sides was prepared. Resin sheets were laminated on both sides of this inner layer substrate so that the resin composition layer was in contact with the inner layer substrate. This lamination was performed using a vacuum pressure laminator (Meiki Seisakusho's "MVLP-500"), with vacuum suction at a temperature of 120°C for 30 seconds, followed by lamination at a temperature of 120°C and a pressure of 7.0 kg / cm. 2 Then, the substrate was pressed for 30 seconds with a heat-resistant rubber between the substrate and the support under atmospheric pressure at a temperature of 120°C and a pressure of 5.5 kg / cm using a stainless steel end plate. 2 The press was performed for 60 seconds under the above conditions.

[0307] (2) Thermal curing of the resin composition layer: The resin composition layer was thermally cured by heating at 130° C. for 30 minutes and then at 170° C. for 30 minutes to obtain an insulating layer as a cured layer made of the cured resin composition. The support was then peeled off to obtain a sample substrate having a layer structure of insulating layer / inner layer substrate / insulating layer.

[0308] (3) Roughening treatment: The insulating layer of the sample substrate was subjected to a roughening treatment. Specifically, the sample substrate was immersed in a swelling solution, Swelling Dip Securigant P (manufactured by Atotech Japan), at 60°C for 10 minutes. Next, it was immersed in a roughening solution, Concentrate Compact P (aqueous solution of KMnO4: 60g / L, NaOH: 40g / L) (manufactured by Atotech Japan), at 80°C for 20 minutes. Finally, it was immersed in a neutralizing solution, Reduction Solution Securigant P (manufactured by Atotech Japan), at 40°C for 5 minutes.

[0309] (4) Crack evaluation: The surface of the insulating layer after the roughening treatment was observed on the wiring pattern of the inner layer board. The surface of the insulating layer was checked for cracks along the pattern shapes of 100 inner layer boards, and the percentage of the number of parts on the pattern where cracks did not occur was counted. This percentage was calculated as the "yield." The calculated yield was also scored according to the following criteria. 1 point: 0% or more but less than 20%. 2 points: 20% or more but less than 40%. 3 points: 40% or more but less than 60%. 4 points: 60% or more but less than 80%. 5 points: 80% or above. A score of 5 or more was evaluated as "○", a score of 3 to 4 was evaluated as "△", and a score of 2 or less was evaluated as "×".

[0310] <Test Example I-3: Evaluation of blister resistance> (1) Surface preparation for interior boards: A glass cloth-based epoxy resin double-sided copper-clad laminate (copper foil thickness 18 μm, substrate thickness 0.8 mm, Panasonic "R1515A") with copper foil on the surface was prepared as an inner layer substrate. The copper foil on the surface of this inner layer substrate was etched with a microetching agent (Mec "CZ8101") with a copper etching amount of 1 μm to perform a roughening treatment. Then, it was dried at 190°C for 30 minutes.

[0311] (2) Lamination and curing of resin sheets: The resin sheet was laminated on both sides of the inner layer substrate using a batch type vacuum pressure laminator (Nikko Materials Co., Ltd. 2-stage build-up laminator "CVP700") so that the resin composition layer was bonded to the inner layer substrate. This lamination was performed by reducing the pressure for 30 seconds to 13 hPa or less, and then pressing at a temperature of 100°C and a pressure of 0.74 MPa for 30 seconds. The laminated resin sheet was then heat pressed at atmospheric pressure, 100°C, and a pressure of 0.5 MPa for 60 seconds to smooth it.

[0312] The laminate was placed in a 130°C oven for 30 minutes and then transferred to a 170°C oven for 30 minutes to thermally cure the resin composition layer, thereby obtaining an insulating layer as a cured layer made of the cured resin composition. The support was then peeled off to obtain an intermediate substrate having a layer structure of insulating layer / inner layer substrate / insulating layer.

[0313] (3) Roughening treatment: The intermediate substrate was immersed in a swelling solution, Swelling Dip Securiganth P (manufactured by Atotech Japan), at 60°C for 10 minutes. Next, it was immersed in a roughening solution, Concentrate Compact P (aqueous solution of KMnO4: 60g / L, NaOH: 40g / L) (manufactured by Atotech Japan), at 80°C for 20 minutes. Finally, it was immersed in a neutralizing solution, Reduction Solution Securiganth P (manufactured by Atotech Japan), at 40°C for 5 minutes. The obtained intermediate substrate was designated as evaluation substrate A.

[0314] (4) Semi-additive plating: In order to form a circuit on the surface of the insulating layer, the evaluation board A was immersed in an electroless plating solution containing PdCl2, and then immersed in an electroless copper plating solution. After heating at 150°C for 30 minutes to perform an annealing treatment, an etching resist was formed, and a pattern was formed by etching. Then, copper sulfate electrolytic plating was performed to form a conductor layer with a thickness of 30±5μm. Next, an annealing treatment was performed at 180°C for 60 minutes. As a result, an evaluation board B was obtained as a circuit board having a conductor layer on an insulating layer.

[0315] (5) Evaluation of blistering during reflow process: The evaluation board B was cut to obtain a small piece of 100 mm x 50 mm. A test was conducted by passing this small piece through a reflow device ("HAS-6116" manufactured by Nippon Antom Co., Ltd.) that reproduces a solder reflow temperature of a peak temperature of 260 ° C. five times (the reflow temperature profile conforms to IPC / JEDEC J-STD-020C). The above test was conducted on five small pieces, and the small pieces after the test were visually observed. As a result of the visual observation, the blister resistance was judged as "x" even though the conductive layer had abnormalities such as swelling in three or more small pieces. In addition, the blister resistance was judged as "△" even though the conductive layer had abnormalities such as swelling in one or two small pieces. Furthermore, the blister resistance was judged as "○" even though there were no abnormalities in all small pieces.

[0316] <Results for Example Group I> The results of the above-mentioned Examples I-1 to I-12 and Comparative Examples I-1 to I-4 are shown in the following Tables 1 to 3. In the following tables, "Compound 1" represents the propenyl resin produced in Synthesis Example 1.

[0317] [Table 1]

[0318] [Table 2]

[0319] [Table 3]

[0320] <Explanation of Example Group II> <Example II-1> 20 parts of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent of about 269 g / eq.) and 10 parts of bisphenol type epoxy resin ("ZX1059" manufactured by Nippon Steel Chemical & Material Co., Ltd., 1:1 mixture of bisphenol A type and bisphenol F type, epoxy equivalent of about 169 g / eq.) were heated and dissolved in 25 parts of solvent naphtha with stirring to obtain a solution. This solution was cooled to room temperature to prepare a dissolved composition of the epoxy resin.

[0321] To this epoxy resin solution, 5 parts of polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industries, average particle size 0.3 μm), 100 parts of an active ester compound ("HPC-8150-62T" manufactured by DIC Corporation, active ester group equivalent of about 220 g / eq., non-volatile content of 62% by mass in toluene solution), and 100 parts of a triazine skeleton-containing phenolic hardener ("LA-3018-50P" manufactured by DIC Corporation, active group equivalent of about 151 g / eq., 2-methoxypropanol solution with non-volatile content of 50%) 10 parts, carbodiimide curing agent (Nisshinbo Chemical Co., Ltd. "V-03", active group equivalent of approximately 216 g / eq., toluene solution with non-volatile content of 50%) 15 parts, spherical silica (Admatechs Co., Ltd. "SO-C2", average particle size 0.5 μm, specific surface area 5.8 m) surface-treated with a silane coupling agent (Shin-Etsu Chemical Co., Ltd. "KBM-573"). 2 A resin composition was prepared by mixing 300 parts of a methyl ketone (MEK) (1:1 solution with a non-volatile content of 30% by mass) and a curing accelerator (4-dimethylaminopyridine (DMAP)) (g), 0.2 parts of a curing accelerator (4-dimethylaminopyridine (DMAP)), and 10 parts of a phenoxy resin (YX7553BH30 manufactured by Mitsubishi Chemical Corporation, a 1:1 solution of MEK and cyclohexanone with a non-volatile content of 30% by mass).

[0322] <Example II-2> The amount of polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industries, Ltd., average particle size 0.3 μm) was increased from 5 parts to 15 parts. Furthermore, instead of 100 parts of an active ester compound ("HPC-8150-62T" manufactured by DIC Corporation, active ester group equivalent of about 220 g / eq., toluene solution with non-volatile content of 62 mass%), 100 parts of an active ester compound ("HPC-8000-65T" manufactured by DIC Corporation, active ester group equivalent of about 223 g / eq., toluene solution with non-volatile content of 65%) was used. A resin composition was prepared in the same manner as in Example II-1 except for the above.

[0323] <Example II-3> Instead of 5 parts of polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industries, average particle size 0.3 μm), 5 parts of polystyrene / acrylic copolymer fine particles ("SEP-03T3A" manufactured by Negami Chemical Industries, average particle size 0.3 μm) were used. In addition, spherical silica ("SO-C2" manufactured by Admatechs Co., Ltd., average particle size 0.5 μm, specific surface area 5.8 m) surface-treated with a silane coupling agent ("KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd.) was used. 2 The amount of cellulose acetate / g was reduced from 300 parts to 210 parts. In addition, 6 parts of hollow aluminosilicate particles ("MG-005" manufactured by Taiheiyo Cement Corporation, hollow inorganic filler, average particle size 1.6 μm, porosity 80% by volume) were added to the resin composition. A resin composition was prepared in the same manner as in Example II-1, except for the above points.

[0324] <Example II-4> Instead of 5 parts of polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industries, average particle size 0.3 μm), 5 parts of polystyrene fine particles to which a carboxy group was added ("XX-6288Z" manufactured by Sekisui Chemical Industries, average particle size 0.3 μm) were used. Furthermore, 3 parts of biphenylaralkylnovolac type maleimide ("MIR-3000-70MT" manufactured by Nippon Kayaku Co., Ltd., MEK / toluene mixed solution with non-volatile content of 70%) were added to the resin composition. A resin composition was prepared in the same manner as in Example II-1 except for the above items.

[0325] <Example II-5> Instead of 5 parts of polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industries, average particle size 0.3 μm), 5 parts of polystyrene fine particles ("GS-0305" manufactured by Aica Kogyo Co., Ltd., average particle size 3.0 μm) were used. In addition, instead of 10 parts of bisphenol type epoxy resin ("ZX1059" manufactured by Nippon Steel Chemical & Material Co., Ltd., 1:1 mixture of bisphenol A type and bisphenol F type, epoxy equivalent of about 169 g / eq.), 10 parts of naphthalene type epoxy resin ("HP-4032-SS" manufactured by DIC Corporation, 1,6-bis(glycidyloxy)naphthalene, epoxy equivalent of about 145 g / eq.) were used. Furthermore, 5 parts of vinylbenzyl modified polyphenylene ether ("OPE-2St 2200" manufactured by Mitsubishi Gas Chemical Co., Ltd., toluene solution with non-volatile content of 65%) were added to the resin composition. A resin composition was prepared in the same manner as in Example II-1 except for the above items.

[0326] <Example II-6> Instead of 5 parts of polystyrene fine particles (Aica Kogyo Co., Ltd. "GS-0305", average particle size 3.0 μm), 5 parts of polyethylene fine particles (Morimura Chemical Co., Ltd. "SB-25", average particle size 2.5 μm) were used. Also, instead of 5 parts of vinylbenzyl-modified polyphenylene ether (Mitsubishi Gas Chemical Co., Ltd. "OPE-2St 2200", toluene solution with non-volatile content of 65%), 3 parts of the propenyl resin obtained in Synthesis Example 1 were used. Except for the above, a resin composition was prepared in the same manner as in Example II-5.

[0327] <Example II-7> Instead of 5 parts of polystyrene fine particles (Aica Kogyo Co., Ltd. "GS-0305", average particle size 3.0 μm), 5 parts of polystyrene fine particles (Negami Chemical Industries Co., Ltd. "SEP-03T3", average particle size 0.3 μm) were used. In addition, the amount of active ester compound (DIC Corporation "HPC-8150-62T", active ester group equivalent of approximately 220 g / eq., toluene solution with non-volatile content of 62 mass%) was reduced from 100 parts to 80 parts. In addition, spherical silica (Admatechs Co., Ltd. "SO-C2", average particle size 0.5 μm, specific surface area 5.8 m) surface-treated with a silane coupling agent (Shin-Etsu Chemical Co., Ltd. "KBM-573") was used. 2 The amount of tertiary amine (1 / g) was reduced from 300 parts to 250 parts. A resin composition was prepared in the same manner as in Example II-5 except for the above.

[0328] <Comparative Example II-1> A resin composition was prepared in the same manner as in Example II-1, except that polystyrene fine particles ("SEP-03T3" manufactured by Negami Chemical Industrial Co., Ltd., average particle size 0.3 μm) were not used.

[0329] <Comparative Example II-2> Instead of 5 parts of polystyrene microparticles ("SEP-03T3" manufactured by Negami Chemical Industries, average particle size 0.3 μm), 5 parts of core-shell structured rubber particles ("Staphyloid AC3816N" manufactured by Aica Kogyo Co., Ltd., core part is acrylic resin, shell part is polymethacrylate resin, average particle size 0.3 μm) were used. In addition, instead of 20 parts of biphenyl type epoxy resin ("NC3000L" manufactured by Nippon Kayaku Co., Ltd., epoxy equivalent of about 269 g / eq.) and 10 parts of bisphenol type epoxy resin ("ZX1059" manufactured by Nippon Steel Chemical & Material Co., Ltd., 1:1 mixture of bisphenol A type and bisphenol F type, epoxy equivalent of about 169 g / eq.), 20 parts of naphthalene type epoxy resin ("HP-4032-SS" manufactured by DIC Corporation, 1,6-bis(glycidyloxy)naphthalene, epoxy equivalent of about 145 g / eq.) and 10 parts of bixylenol type epoxy resin ("YX4000H" manufactured by Mitsubishi Chemical Corporation, epoxy equivalent of 190 g / eq.) were used. A resin composition was prepared in the same manner as in Example II-1 except for the above.

[0330] <Comparative Example II-3> Instead of 5 parts of rubber particles (Aica Kogyo Co., Ltd.'s "Staphyloid AC3816N", average particle size 0.3 μm), 5 parts of polystyrene particles (Negami Chemical Industries Co., Ltd.'s "G-800T", average particle size 6.0 μm) were used. Except for the above, a resin composition was prepared in the same manner as in Comparative Example II-2.

[0331] <Production of resin sheets> A polyethylene terephthalate film with a release layer ("AL5" manufactured by Lintec Corporation, thickness 38 μm) was prepared as a support. The resin compositions obtained in the above-mentioned Examples and Comparative Examples were uniformly applied onto the release layer of this support so that the thickness of the resin composition layer after drying was 40 μm. Thereafter, the resin composition was dried at 80°C to 100°C (average 90°C) for 4 minutes to obtain a resin sheet including a support and a resin composition layer.

[0332] <Test Example II-1: Measurement of relative dielectric constant (Dk) and dielectric loss tangent (Df)> The resin sheet was heated at 200°C for 90 minutes to heat-cure the resin composition layer, and then the support was peeled off to obtain a cured film formed of the cured product of the resin composition. The cured film was cut into a size of 62 mm x 75 mm to obtain a cured product A for evaluation.

[0333] The dielectric loss tangent and relative dielectric constant of the obtained cured product A for evaluation were measured at a measurement frequency of 10 GHz by a split cylinder resonance method using "CR-710" manufactured by EM Lab Co., Ltd. The dielectric loss tangent was measured at 25°C and 100°C. The relative dielectric constant was measured at 25°C.

[0334] The rate of increase of the dielectric tangent Df(100°C) at 100°C relative to the dielectric tangent Df(25°C) at 25°C was calculated as {Df(100°C)-Df(25°C)} / Df(25°C). If this rate of increase was less than 20%, the temperature stability of the dielectric tangent at high temperatures was judged as "Good." If the rate of increase was 20% or more, the temperature stability of the dielectric tangent at high temperatures was judged as "Poor."

[0335] <Test Example II-2: Evaluation of crack resistance> According to the method described in <Test Example I-2: Evaluation of crack resistance> in the description of Example Group I, the resin compositions produced in each of the Examples and Comparative Examples were used to form an insulating layer and evaluate cracking.

[0336] <Test Example II-3: Evaluation of insulation reliability> The resin sheet was laminated onto a TAB tape (tape used for tape automated bonding) with L / S=20μm / 20μm using a batch type vacuum laminator ("VP160" manufactured by Nichigo Morton Co., Ltd.). After peeling off the support, the resin composition layer was cured by heating at 180°C for 90 minutes in a batch type oven to obtain a sample having a layer structure of TAB tape / insulating layer. The resistance value of the insulating layer was measured at seven points. The resistance value of the insulating layer measured in this manner is referred to as the "initial resistance value."

[0337] Next, the sample was subjected to a HAST test in which the sample was left in a HAST tester (Kusumoto Chemical Industries, Ltd., "ETAC PM422") under conditions of 130°C and 85% Rh for 100 hours. After this HAST test, the resistance value of the insulating layer of the sample was measured at seven points. The resistance value of the insulating layer measured in this way is called the "resistance value after HAST."

[0338] The standard for insulation is a resistance value of 1.0 x 10 6 Ω or more is good, 1.0×10 6 Based on this standard, the insulation reliability was evaluated according to the following criteria. ○: Six or more samples had good insulation for both the initial resistance value and the resistance value after HAST. △: Five samples had good insulation both in terms of initial resistance and resistance after HAST. ×: Fewer than five samples had good insulation both in terms of the initial resistance value and the resistance value after HAST.

[0339] <Results for Example Group II> The results of the above-mentioned Examples II-1 to II-7 and Comparative Examples II-1 to II-3 are shown in Tables 4 and 5 below.

[0340] [Table 4]

[0341] [Table 5] [Explanation of symbols]

[0342] 100 Semiconductor chip package 110 Semiconductor Chip 120 Sealing layer 130 Rewiring formation layer 140 Redistribution layer 150 Solder resist layer 160 Bump < / ii-14> < / ii-1> < / ii-13> < / ii-1> < / ii-12> < / ii-1> < / ii-1> < / ii-10> < / ii-1> < / ii-9> < / ii-1> < / ii-1> < / ii-1> < / ii-1> < / ii-1> < / i-12> < / i-1> < / i-11> < / i-1> < / i-10> < / i-1> < / i-1> < / i-8> < / i-1> < / i-7> < / i-1> < / i-1> < / i-1>

Claims

1. (A) an organic filler including a polymer containing a repeating unit represented by the following formula (1), and (B) a curable resin, (A) the average particle size of the organic filler is 5 μm or less; (B) the curable resin contains an epoxy resin and an active ester resin; (A) the amount of the organic filler is 0.2% by mass or more and 40% by mass or less, based on 100% by mass of the resin component of the resin composition; The amount of the epoxy resin is 5% by mass or more and 80% by mass or less, based on 100% by mass of the resin component of the resin composition; A resin composition, comprising an active ester resin in an amount of 1% by mass or more and 80% by mass or less, based on 100% by mass of the resin component of the resin composition. 【Chemistry 1】 (In formula (1), R a each independently represents a hydrogen atom or a monovalent saturated hydrocarbon group, R b represents a monovalent aromatic hydrocarbon group which may have a substituent.

2. The resin composition according to claim 1 , further comprising (C) an inorganic filler.

3. The resin composition according to claim 1, wherein the curable resin (B) comprises at least one resin selected from the group consisting of a phenolic resin, a cyanate resin, a (meth)acrylic resin, a styryl resin, a propenyl resin, and a maleimide resin.

4. (A) a particle of the organic filler includes a shell portion exposed on a surface of the particle of the organic filler, The resin composition according to claim 1 , wherein the shell portion comprises a polymer containing a repeating unit represented by formula (1).

5. The resin composition according to claim 1, wherein the organic filler (A) has an average particle size of 1 μm or less.

6. The rate of increase of Df(100°C) relative to Df(25°C) is less than 20%, Df (25°C) represents the dielectric tangent at 25°C of a cured product obtained by heat-treating a resin composition at 200°C for 90 minutes, The resin composition according to claim 1, wherein Df (100°C) represents the dielectric tangent at 100°C of a cured product obtained by heat-treating the resin composition at 200°C for 90 minutes.

7. The resin composition according to claim 1, wherein the amount of the organic filler (A) is 0.2 mass % or more and 5 mass % or less based on 100 mass % of the nonvolatile components of the resin composition.

8. The resin composition according to claim 1 , which is for forming an insulating layer.

9. A cured product of the resin composition according to any one of claims 1 to 8.

10. A sheet-like laminate material comprising the resin composition according to any one of claims 1 to 8.

11. A support and a resin composition layer formed on the support, A resin sheet, wherein the resin composition layer comprises the resin composition according to any one of claims 1 to 8.

12. A circuit board comprising a cured product of the resin composition according to any one of claims 1 to 8.

13. A semiconductor chip package comprising a cured product of the resin composition according to any one of claims 1 to 8.

14. A semiconductor device comprising the circuit board according to claim 12.

15. A semiconductor device comprising the semiconductor chip package according to claim 13.

Citation Information

Patent Citations

  • Resin composition

    JP2017165876A

  • Thermosetting resin composition, dry film, cured product, and electronic component

    JP2019167426A

  • Resin material and multilayer printed board

    JP2020023714A

  • Resin composition

    JP2020083966A

  • Manufacturing method of print circuit board

    JP2020136542A